Battery separators, batteries including separators, and methods and systems for forming same
By incorporating a condensation polymer and using controlled vapor environments, the manufacturing of microporous sheet products for battery separators achieves enhanced porosity and reduced water interaction, addressing porosity limitations and lithium-ion battery degradation issues.
Patent Information
- Application Number
- CN202411297797.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2020-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
Existing methods for manufacturing microporous sheet products for battery separators are limited in porosity control and often result in reduced ionic conductivity due to surface layers formed during processing, and lithium-ion batteries face issues with water ingress leading to undesirable reactions that degrade performance and pose environmental hazards.
Incorporating a condensation polymer, such as polyamide, into the microporous sheet product that undergoes molecular weight reduction upon exposure to water, and using specific manufacturing methods involving controlled vapor environments to form a microporous sheet with enhanced porosity and reduced water interaction.
The solution minimizes undesirable reactions in lithium-ion batteries by scavenging water and acid, maintaining ionic conductivity, and extending battery life while being environmentally friendly.
Smart Images

Figure CN119208912A_ABST
Abstract
Description
[0001] This application is a divisional application. The application date of the original application is August 27, 2020, the application number is 202080074067.3, and the name of the invention is “Battery separator, battery including a separator, and method and system for forming the same”, which is incorporated herein by reference in its entirety.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 892,283 filed on August 27, 2019 by inventor William Winchin Yen, and U.S. Provisional Patent Application No. 62 / 966,862 filed on January 28, 2020 by inventor William Winchin Yen, pursuant to 35 U.S.C. 119(e), the disclosures of which are incorporated herein by reference. Technical Field
[0004] The present invention relates generally to microporous sheet products and, more particularly, to novel microporous sheet products, use of the microporous sheet products as battery separators, electrochemical cells including the battery separators, and novel methods and systems for forming the microporous sheet products. Background Art
[0005] Microporous sheet products are well-known items and are commonly used in various projects, such as electrochemical batteries, food packaging materials, and ultrafiltration devices. For example, in electrochemical batteries, microporous sheet products are commonly used as battery separators. Typically, an electrochemical battery includes a single electrochemical unit (cell) or a plurality of electrochemical units electrically connected to each other and housed in a common housing. Each electrochemical unit typically includes a pair of electrodes of opposite polarity. The current between the pair of electrodes is maintained by an electrolyte. Depending on the nature of the battery system, the electrolyte can be acidic, alkaline, or substantially neutral. Typically, a battery separator is provided between electrodes of opposite polarity in each cell of an electrochemical battery to prevent direct contact between oppositely charged electrode plates, as such direct contact can cause a short circuit in the cell.
[0006] In general, it is highly desirable that the separator has one or more of the following properties: (i) be thin and lightweight to help provide a high energy density cell; (ii) have a structure that inhibits the formation of dendrites between the electrode plates; (iii) have the ability to enhance the uptake of the electrolyte composition on the electrode plates, and in this case, promote a substantially uniform distribution of the electrolyte composition on the electrode plates (an effect generally referred to as wicking); (iv) provide properties that freely allow the electrolyte to conduct electricity. It is further highly desirable that the separator be prepared in an economical and environmentally safe manner while being substantially free of defects, such as pinholes, etc.
[0007] A common type of battery separator includes a microporous sheet product formed by extruding a composition including a polyolefin and a liquid plasticizer, and then removing the plasticizer to produce a sheet having a microporous structure. Typically, such plasticizers are made of high molecular weight oils and the like, the idea being that such plasticizers provide properties compatible with the polymer material during the initial step of sheet formation, while being incompatible and easily extractable during the subsequent sheet formation step. Extraction is typically accomplished by washing the plasticizer from the cooled initially formed sheet using a compatible low molecular weight second liquid. The voids created by the removal of the plasticizer provide a substantially uniform porosity throughout the resulting separator sheet product. The resulting mixed liquid is a waste byproduct of the process. An example of a separator made by this method is disclosed in U.S. Patent No. 4,287,276 to inventors Lundquist, Jr. et al., issued September 1, 1981, which is incorporated herein by reference.
[0008] Another technique for forming a microporous sheet product includes stretching and annealing a polyolefin sheet to produce micropores in the treated sheet. Examples of such techniques are disclosed in the following documents, all of which are incorporated herein by reference: U.S. Patent No. 3,426,754, inventor Bierenbaum et al., issued February 11, 1969; U.S. Patent No. 3,558,764, inventor Isaacson et al., issued January 26, 1971; U.S. Patent No. 3,679,538, inventor Druin et al., issued July 25, 1972; U.S. Patent No. 4,994,335, inventor Kamaei et al., issued February 19, 1991; and U.S. Patent No. 5,328,760, inventor Gillberg-LaForce, issued July 12, 1994.
[0009] Another example of the above technology is disclosed in U.S. Pat. No. 3,679,540 issued on July 25, 1972 to inventors Zimmerman et al., and incorporated herein by reference. In the above patent, a method for preparing an open microporous polymer film from a nonporous crystalline elastic polymer starting film is disclosed, the method comprising (1) cold stretching, i.e., cold drawing, the elastic film until a porous surface area or region elongated orthogonal or perpendicular to the stretching direction is formed, (2) hot stretching, i.e., hot stretching, the cold stretched film until fibrils and pores or openings elongated parallel to the stretching direction are formed, and thereafter (3) heating or heat setting the resulting porous film under tension, i.e., at a substantially constant length, to impart stability to the film. According to the patent, the elastic starting film is preferably prepared from a crystalline polymer (such as polypropylene) by extruding the polymer melt into a film, drawing the extrudate to obtain an oriented film at a drawdown ratio, and then heating or annealing the oriented film if necessary to improve or enhance the initial crystallinity.
[0010] The present inventors have recognized that one disadvantage of the above techniques is that, in practice, the porosity of the resulting films is typically limited to less than about 40% and is not well controlled.
[0011] Other techniques for forming microporous sheet products are disclosed in other patents and publications. For example, in U.S. Pat. No. 5,503,791, issued on April 2, 1996 to inventors Fortuin et al., a method for forming a polyethylene microporous film is disclosed, which is incorporated herein by reference. According to the above patent, the method involves extruding a solution of a polyolefin in a first solvent, followed by cooling, removing the solvent, and stretching the film, wherein both sides of the film are initially in close contact with a second solvent for the polyolefin, and then the film is contacted with a coolant (e.g., water).
[0012] In U.S. Patent No. 9,159,978B2 issued on October 13, 2015 to inventor Yen, a sheet product and a method of forming a sheet product suitable for use as a battery separator are disclosed, which is incorporated herein by reference. The method includes forming a mixture of a thermoplastic polymer and a fluid having a high vapor pressure, forming the mixture into a sheet material, and subjecting the sheet material to stretching / fluid evaporation at a high temperature to form an intermediate material having a ratio of fluid percentage to polymer crystallinity percentage between 0.15 and 1, followed by secondary stretching / fluid evaporation at a low temperature while removing a portion of the fluid residue from the sheet. The resulting sheet is annealed and the fluid residue is removed to form a sheet product having a thickness of a layered structure including small and larger pore layered structures across its thickness.
[0013] U.S. Patent No. 8,486,555B2, issued on July 16, 2013 to inventors Usami et al., discloses a method for producing a porous laminate having many interconnected micropores in the thickness direction, which is incorporated herein by reference, and comprises: a step of producing a laminate comprising at least three layers, the three layers comprising an intermediate layer made of a thermoplastic resin having a hard segment and a soft segment and two non-porous outer layers made of a filler-containing resin and respectively serving as outer layers on both sides of the interlayer; a step of impregnating the obtained laminate with a supercritical or subcritical fluid and releasing the state to allow the fluid to evaporate and thereby make the intermediate layer porous; and a step of making the two non-porous outer layers respectively located on both sides porous by stretching.
[0014] In U.S. Patent No. 10,586,965B2 issued on March 10, 2020 to inventor Yen, a microporous sheet product is disclosed, which is manufactured by a process comprising melt extruding a sheet using an extrusion mixture, which is incorporated herein by reference, and the extrusion mixture includes (i) a cyclic olefin copolymer, (ii) an electrolyte swellable thermoplastic, and (iii) a compatibilizing agent that promotes mixing of the cyclic olefin copolymer and the electrolyte swellable thermoplastic. For example, the cyclic olefin copolymer can be an ethylene-norbornene copolymer, the electrolyte swellable thermoplastic can be polyethylene oxide, and the compatibilizing agent can be mineral spirits.
[0015] In U.S. Patent Application Publication No. US2007 / 0092777A1, issued on April 26, 2007 by inventors Zhamu et al., a self-humidifying proton exchange membrane (PEM) composition is disclosed, which is incorporated herein by reference, and the composition comprises (a) a proton conducting polymer; (b) a catalyst that promotes a chemical reaction between hydrogen and oxygen molecules to generate water in the membrane, and (c) a deliquescent substance dispersed in the polymer. The deliquescent material absorbs and maintains a substantially constant amount of water to maintain proton mobility in the PEM structure.
[0016] Other documents that may be of interest may include the following, all of which are incorporated herein by reference: U.S. Patent Application Publication No. US2017 / 0166716 A1, inventor Yen, published on June 15, 2017; and U.S. Patent Application Publication No. US2017 / 0152359 A1, inventor Yen, published on June 1, 2017.
[0017] Prior art for separator manufacturing typically requires the steps of casting and extracting low volatility plasticizer oil from the separator network. Such technology often uses chilled rolls to directly contact the extrusion cast separator substrate. However, when using such chilled rolls, a surface layer of 30 to 50 microns thick is usually formed on the sheet surface, which is undesirable. Such surface layers, which are well known in the membrane industry, result in smaller porosity and pore size on the sheet surface, thereby resulting in reduced ionic conductivity for battery applications.
[0018] There are many types of lithium-based primary and secondary electrochemical storage systems, examples of which include, but are not limited to, lithium thionyl chloride systems, lithium manganese dioxide systems, lithium iron sulfide systems, and lithium ion phosphate systems. Among the various lithium-based electrochemical storage systems, one of the more common types is often referred to as a lithium-ion battery. A lithium-ion battery may include a single lithium-ion cell, or, alternatively, may include a plurality of electrically connected lithium-ion cells. Each cell of a lithium-ion battery typically includes an anode, a cathode, an electrolyte, and a separator. The anode is typically made of carbon, such as graphite. The cathode is typically made of a metal oxide, such as LiCoO2 or LiMn2C4. The electrolyte typically contains an organic solvent in which a lithium salt is dissolved. For example, the organic solvent is often a mixture of organic carbonates, such as a mixture of ethylene carbonate and diethyl carbonate. The lithium salt may be lithium hexafluorophosphate (LiPF6).
[0019] Pure lithium is highly reactive, reacting violently with water to form substances such as lithium hydroxide and hydrogen gas. Hydrofluoric acid may also be produced. It is understood that the production of lithium hydroxide, hydrogen gas and hydrofluoric acid in lithium-ion cells is highly undesirable because these products can impair cell performance, as well as present environmental hazards if leaked from the cell. It is for this reason that the electrolyte solvent in lithium-ion cells is typically a non-aqueous electrolyte of the type described above. In addition, in order to minimize the possibility of lithium reacting with water, the components of the cell are typically housed in a sealed container that is intended to prevent water from entering the cell. However, despite these efforts, some water typically enters the cell, or is trapped in one or more of the battery components, such as the metal oxide cathode, often during cell assembly. Some manufacturers attempt to address this problem by vacuum drying the cell at elevated temperatures for a period of time (e.g., 8 hours at 85°C) as part of the battery manufacturing process. However, even after such drying, and even at concentrations as low as 10 ppm, water can begin to catalyze many degradation products that may impair cell performance or may present environmental risks. Summary of the invention
[0020] According to one aspect of the present invention, a lithium-based battery cell is provided, comprising: (a) an electrolyte comprising a non-aqueous solvent and a lithium salt, the lithium salt being dissolved in the non-aqueous solvent; (b) an anode, the anode being in contact with the electrolyte; (c) a cathode, the cathode being in contact with the electrolyte; (d) a battery separator, the battery separator separating the anode and the cathode, wherein the battery separator is a microporous sheet product comprising a first polymer and a second polymer, the first polymer comprising a thermoplastic polymer, the second polymer comprising a condensation polymer produced in a dehydration polymerization reaction and undergoing a molecular weight reduction when exposed to water, wherein at the completion of unit manufacturing, the second polymer has an initial total weight; and (e) a housing, wherein the electrolyte, the anode, the cathode and the battery separator are arranged in the housing; (f) wherein, at the completion of unit manufacturing, an initial amount of water having an initial total weight is present in the housing, and wherein the ratio of the initial total weight of the second polymer to the initial total weight of water is in the range of about 10:1 to 5,000:1.
[0021] In further detailed features of the invention, the first polymer may comprise at least one polyolefin.
[0022] In a more detailed feature of the present invention, the at least one polyolefin may be selected from at least one polyolefin homopolymer, at least one polyolefin copolymer, at least one polyolefin terpolymer, and combinations thereof.
[0023] In a more detailed feature of the present invention, the at least one polyolefin may be selected from polyethylene, polypropylene, ethylene-butene copolymers, ethylene-hexene copolymers, and combinations thereof.
[0024] In a more detailed feature of the invention, the at least one polyolefin may be selected from polyethylene homopolymers, polypropylene homopolymers and copolymers thereof having up to about 10 wt. % of other α-olefins as comonomer units therein.
[0025] In further detailed features of the invention, the at least one polyolefin can have an average molecular weight of about 100,000 to 10,000,000 Da.
[0026] In further detailed features of the invention, the second polymer may have a minimum entanglement molecular weight of at least 1000 Da.
[0027] In a further detailed feature of the invention, the second polymer may have a minimum entanglement molecular weight of at least 4000 Da.
[0028] In a more detailed feature of the invention, a microporous sheet product can be prepared by a method comprising (a) melt extruding an extrusion mixture to form a sheet material, the extrusion mixture comprising (i) a first polymer, (ii) a second polymer and (iii) a compatibilizing agent that promotes mixing of the first and second polymers; and (b) then cooling the sheet material, thereby forming micropores in the sheet material.
[0029] In further detailed features of the invention, the second polymer may experience a reduction in average molecular weight of between 20% and 90% after exposure to water.
[0030] In a more detailed feature of the invention, the second polymer can be selected from polyamides, polyethers, polyesters, polyethylene oxides, polyethylene glycols, polypropylene glycols, polycarbonates, polyanhydrides, polyimides, polybenzimidazoles, polyacetals, polysulfones, polyphenylene oxides and polyurethanes.
[0031] In further detailed features of the present invention, the second polymer may include at least one of a copolymer and a terpolymer.
[0032] In a more detailed feature of the present invention, the second polymer may include a mixture of at least two polymers, and at least one of the at least two polymers may be a copolymer.
[0033] In a more detailed feature of the invention, the initial weight ratio of the copolymer polycondensate to the total polycondensate may be from 0.1:1 to 0.9:1.
[0034] In a more detailed feature of the invention, the initial weight ratio of the copolymer polycondensate to the total polycondensate may be from 0.2:1 to 0.85:1.
[0035] In a more detailed feature of the invention, the initial weight ratio of the copolymer polycondensate to the total polycondensate may be from 0.3:1 to 0.8:1.
[0036] In a further detailed feature of the invention, the second polymer may comprise at least one polyamide.
[0037] In a more detailed feature of the invention, the at least one polyamide may be selected from at least one homopolymer, at least one copolymer, at least one terpolymer and combinations thereof.
[0038] In a further detailed feature of the invention, the at least one polyamide may have a relative viscosity compared to m-cresol of at least 1.4:1.
[0039] In a further detailed feature of the invention, the ratio of the initial total weight of the second polymer to the initial total weight of water is at least 50:1.
[0040] In a further detailed feature of the invention, the ratio of the initial total weight of the second polymer to the initial total weight of water is at least 500:1.
[0041] In further detailed features of the invention, the second polymer can have an initial average molecular weight of at least 12,000 Da.
[0042] In further detailed features of the invention, the second polymer can have an initial average molecular weight of at least 20,000 Da.
[0043] In further detailed features of the invention, the second polymer can have an initial average molecular weight of at least 29,000 Da.
[0044] In a more detailed feature of the invention, the second polymer may be selected from polyoxyethylene and polypropylene glycol.
[0045] In a further detailed feature of the invention, the second polymer can have an initial molecular weight of at least 110,000 Da.
[0046] In a further detailed feature of the invention, the second polymer can have an initial molecular weight of at least 310,000 Da.
[0047] In a further detailed feature of the invention, the second polymer can have an initial molecular weight of at least 910,000 Da.
[0048] In a further detailed feature of the invention, the second polymer can have an initial molecular weight of at least 2,100,000 Da.
[0049] In a more detailed feature of the present invention, the second polymer and the first polymer may have an initial average molecular weight ratio of less than 2:1 and greater than 0.01:1.
[0050] In a more detailed feature of the present invention, the second polymer and the first polymer may have an initial average molecular weight ratio of less than 1:1.
[0051] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial average molecular weight ratio of less than 0.5:1.
[0052] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial average molecular weight ratio of less than 0.2:1.
[0053] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial weight ratio between 0.01:1 and 1:1.
[0054] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial weight ratio between 0.02:1 and 0.5:1.
[0055] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial weight ratio between 0.05:1 and 0.3:1.
[0056] In a more detailed feature of the invention, the second polymer and the first polymer may have an initial weight ratio between 0.1:1 and 0.2:1.
[0057] In a more detailed feature of the invention, the compatibilizing agent may include at least one organic fluid, the first polymer may constitute approximately 10-60 weight percent of the extrusion mixture, the second polymer may constitute approximately 2.1-9.9 weight percent of the extrusion mixture, and the compatibilizing agent may constitute approximately 40 to 75 weight percent of the extrusion mixture.
[0058] In a more detailed feature of the present invention, the compatibilizing agent may be at least one selected from hydrocarbon oils, organic esters, and phthalates.
[0059] In a more detailed feature of the invention, the compatibilizing agent has a vapor pressure of about 1 to 50 mm Hg at 70°C, a vapor pressure of about 0.1 to 5 mm Hg at 20°C, and a boiling temperature of about 170 to 250°C, and wherein the compatibilizing agent may include a fluid mixture having a boiling range as wide as at least 20°C.
[0060] In further detailed features of the invention, the ratio of the average initial molecular weight of the second polymer to the average final molecular weight of the second polymer can be at least 1:1 and less than 1000:1.
[0061] In a further detailed feature of the invention, the lithium-based battery cell may initially contain greater than 10 ppm of water.
[0062] In a further detailed feature of the invention, the lithium-based battery cell may initially contain greater than 40 ppm of water.
[0063] According to another aspect of the present invention, a lithium-based battery cell is provided, comprising: (a) an electrolyte comprising a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent; (b) an anode in contact with the electrolyte; (c) a cathode in contact with the electrolyte; (d) a battery separator separating the anode from the cathode, wherein the battery separator is a microporous sheet product comprising a first polymer and a second polymer, the first polymer comprising a thermoplastic polymer, the second polymer comprising a condensation polymer produced in a dehydration polymerization reaction and undergoing a molecular weight reduction when exposed to water, wherein at the completion of unit manufacturing, the second polymer has an initial total weight; and (e) a housing, wherein the electrolyte, the anode, the cathode and the battery separator are arranged in the housing; (f) wherein, at the completion of unit manufacturing, an initial amount of water is present in the housing, and wherein the second polymer reacts with substantially all of the initial amount of water to undergo a molecular weight reduction of about 20% to 90% and wherein the second polymer has a minimum entanglement molecular weight of at least 1000 Da.
[0064] According to another aspect of the present invention, there is provided a microporous sheet product, which is prepared by a method comprising: (a) melt extruding an extrusion mixture to form a cast sheet, wherein the extrusion mixture comprises: at least one thermoplastic polymer and a compatibilizing agent, the compatibilizing agent comprising a first organic fluid; (b) cooling the cast sheet in a first gas region, the first gas region comprising a first organic vapor, the first organic vapor comprising the first organic fluid in vapor form, the first organic vapor being present in at least a portion of the first gas region at a concentration above the UEL; and (c) performing at least some stretching on the cooled cast sheet in a second gas region, the second gas region comprising a second organic vapor, the second organic vapor comprising the first organic fluid in vapor form, the second organic vapor being present in the second gas region at a concentration below the LEL.
[0065] In further detailed features of the invention, the at least one thermoplastic polymer may include at least one polyolefin.
[0066] In a more detailed feature of the present invention, the at least one polyolefin may be selected from at least one polyolefin homopolymer, at least one polyolefin copolymer, at least one polyolefin terpolymer, and combinations thereof.
[0067] In a more detailed feature of the present invention, the at least one polyolefin may be selected from polyethylene, polypropylene, ethylene-butene copolymers, ethylene-hexene copolymers, and combinations thereof.
[0068] In a more detailed feature of the invention, the at least one polyolefin may be selected from polyethylene homopolymers, polypropylene homopolymers and copolymers thereof, and copolymers thereof having up to about 10 wt. % of other α-olefins as comonomer units therein.
[0069] In further detailed features of the invention, the at least one polyolefin can have an average molecular weight of about 100,000 to 10,000,000 Da.
[0070] In a more detailed feature of the invention, the extrusion mixture can further comprise at least one condensation polymer, and the at least one condensation polymer can undergo a molecular weight reduction when exposed to water.
[0071] In further detailed features of the invention, at least one condensation polymer may have a minimum entanglement molecular weight of at least 1000 Da.
[0072] In further detailed features of the invention, at least one condensation polymer may have a minimum entanglement molecular weight of at least 4000 Da.
[0073] In a further detailed feature of the invention, upon exposure to water, at least one condensation polymer can undergo a reduction in average molecular weight of between 20% and 90%.
[0074] In a more detailed feature of the present invention, the at least one condensation polymer can be at least one selected from polyamide, polyether, polyester, polyethylene oxide, polyethylene glycol, polypropylene glycol, polycarbonate, polyanhydride, polyimide, polybenzimidazole, polyacetal, polysulfone, polyphenylene ether and polyurethane.
[0075] In further detailed features of the invention, the at least one condensation polymer may include at least one of a copolymer and a terpolymer.
[0076] In a further detailed feature of the invention, the at least one condensation polymer may include a mixture of at least two polymers, and at least one of the at least two polymers may be a copolymer.
[0077] In a more detailed feature of the invention, the initial weight ratio of the copolymer polycondensate to the total polycondensate may be from 0.1:1 to 0.9:1.
[0078] In a more detailed feature of the invention, the initial weight ratio of the copolymer polycondensate to the total polycondensate may be from 0.3:1 to 0.8:1.
[0079] In a further detailed feature of the invention, the at least one polycondensate may comprise at least one polyamide.
[0080] In a more detailed feature of the invention, the at least one polyamide may be selected from at least one homopolymer, at least one copolymer, at least one terpolymer and combinations thereof.
[0081] In a further detailed feature of the invention, the at least one polyamide may have a relative viscosity compared to m-cresol of at least 1.4:1.
[0082] In a further detailed feature of the invention, the at least one polyamide can have a relative viscosity compared to m-cresol of at least 1.9:1.
[0083] In a further detailed feature of the invention, at least one condensation polymer can have an initial average molecular weight of at least 12,000 Da.
[0084] In further detailed features of the invention, at least one condensation polymer can have an initial average molecular weight of at least 29,000 Da.
[0085] In a more detailed feature of the invention, the at least one condensation polymer may be selected from polyoxyethylene and polypropylene glycol.
[0086] In a further detailed feature of the invention, at least one condensation polymer can have an initial molecular weight of at least 110,000 Da.
[0087] In further detailed features of the invention, at least one condensation polymer can have an initial molecular weight of at least 2,100,000 Da.
[0088] In a more detailed feature of the invention, the at least one condensation polymer and the at least one thermoplastic polymer may have an initial average molecular weight ratio lower than 2:1 and higher than 0.01:1.
[0089] In a further detailed feature of the invention, the at least one condensation polymer and the at least one thermoplastic polymer may have an initial average molecular weight ratio of less than 0.2:1.
[0090] In a more detailed feature of the invention, the at least one condensation polymer and the at least one thermoplastic polymer may have an initial weight ratio between 0.01:1 and 1:1.
[0091] In a more detailed feature of the invention, the at least one polycondensate and the at least one thermoplastic polymer may have an initial weight ratio between 0.1:1 and 0.2:1.
[0092] In a more detailed feature of the present invention, the compatibilizing agent may be at least one selected from hydrocarbon oils, organic esters, and phthalates.
[0093] In a more detailed feature of the invention, the compatibilizing agent has a vapor pressure of about 1 to 50 mm Hg at 70°C, a vapor pressure of about 0.1 to 5 mm Hg at 20°C, and a boiling temperature of about 170 to 250°C.
[0094] In a further detailed feature of the invention, the compatibilizing agent may include a fluid mixture having a boiling range as broad as at least 20°C.
[0095] In a further detailed feature of the invention, the extrusion mixture may be composed of at least one thermoplastic polymer and a compatibilizing agent.
[0096] In a more detailed feature of the invention, the extrusion mixture may be composed of at least one thermoplastic polymer, at least one polycondensate and a compatibilizing agent.
[0097] In a further detailed feature of the invention, the first organic vapor can consist of the first organic fluid in vapor form.
[0098] In a further detailed feature of the invention, the first organic vapor can include a first organic fluid in vapor form and a second organic fluid in vapor form.
[0099] In a further detailed feature of the invention, the first gas region may be maintained at a temperature in the range of -20°C to 160°C.
[0100] In a further detailed feature of the invention, the cast sheet may reside in the first gas zone for a period of time ranging from 0.01 to 20 seconds.
[0101] In further detailed features of the invention, the first organic vapor can be present in the first gas region at a concentration of at least 3 volume percent.
[0102] In further detailed features of the invention, the first organic vapor can be present in the first gas region at a concentration of at least 7 volume percent.
[0103] In further detailed features of the invention, the first organic vapor can be present in the first gas region at a concentration of at least 15 volume percent.
[0104] In further detailed features of the invention, the first organic vapor can be present in the first gas region at a concentration of at least 30 volume percent.
[0105] In a further detailed feature of the invention, the first gas region may be enclosed by a housing.
[0106] In a more detailed feature of the invention, a concentration ratio of the first organic vapor to oxygen in the first gas region may be greater than 0.1:1.
[0107] In a more detailed feature of the invention, a concentration ratio of the first organic vapor to oxygen in the first gas region may be greater than 0.5:1.
[0108] In a more detailed feature of the present invention, a concentration ratio of the first organic vapor to oxygen in the first gas region may be greater than 1:1.
[0109] In a more detailed feature of the invention, a concentration ratio of the first organic vapor to oxygen in the first gas region may be greater than 2:1.
[0110] According to another aspect of the present invention, there is provided a method for manufacturing a microporous sheet product, the method comprising the following steps:
[0111] (a) melt extruding an extrusion mixture to form a cast sheet, wherein the extrusion mixture comprises at least one thermoplastic polymer and a compatibilizing agent, the compatibilizing agent comprising a first organic fluid;
[0112] (b) cooling the cast sheet in a first gas region, the first gas region comprising a first organic vapor, the first organic vapor comprising a first organic fluid in vapor form, the first organic vapor being present in at least a portion of the first gas region at a concentration above the UEL; and
[0113] (c) subjecting the cooled cast sheet to at least some stretching in a second gas zone comprising a second organic vapor comprising the first organic fluid in vapor form, the second organic vapor being present in the second gas zone at a concentration below the LEL.
[0114] In further detailed features of the invention, the first organic vapor can be present in the first gas region at a concentration of at least 3 volume percent.
[0115] In a more detailed feature of the invention, a concentration ratio of the first organic vapor to oxygen in the first gas region may be greater than 0.1:1.
[0116] In a further detailed feature of the invention, some of the first organic vapor may condense on the casting roll to form a fluid condensate surface thereon, and the cooling step may include cooling the cast sheet on the condensate surface on the casting roll.
[0117] In a further detailed feature of the invention, the above-UEL concentration may be achieved by ambient oxygen egress from an enclosure defining the first gas zone.
[0118] In a further detailed feature of the invention, the housing can be configured to minimize the ingress of water vapor therein.
[0119] In a further detailed feature of the invention, the melt extrusion step may include increasing the extruder energy input by increasing the extruder screw rpm and / or by adding kneading blocks.
[0120] In further detailed features of the invention, the first organic vapor can be present at a concentration above the UEL throughout the entirety of the first gas zone.
[0121] In further detailed features of the invention, the first organic vapor may be present in only a portion of the first gas zone at a concentration above the UEL.
[0122] In a more detailed feature of the invention, the first gas region can be defined by a housing, cooling can be provided by at least one chilled roll, and the first organic vapor can be present at a concentration above the UEL starting at or near an inlet of the housing and extending around the chilled roll.
[0123] According to another aspect of the present invention, a method is provided, the method comprising the steps of: (a) providing a microporous sheet product, the microporous sheet product comprising a first polymer and a second polymer, the first polymer comprising a thermoplastic polymer, the second polymer comprising a condensation polymer produced in a dehydration polymerization reaction and undergoing a molecular weight reduction when exposed to water; and (b) incorporating the microporous sheet product into an electrochemical cell, wherein an initial amount of water having an initial total weight is present in the electrochemical cell when the cell is manufactured, and wherein the ratio of the initial total weight of the second polymer to the initial total weight of the water is in the range of about 10:1 to 5,000:1.
[0124] In further detailed features of the invention, the second polymer may have a minimum entanglement molecular weight of at least 1000 Da.
[0125] According to another aspect of the present invention, a system for making a microporous sheet product is provided.
[0126] In a more detailed feature of the invention, the system may include (a) an extruder, (b) a die head positioned at an outlet end of the extruder for discharging a cast sheet, (c) a first gas region, the first gas region being configured to receive the cast sheet from the die head and to cool the cast sheet, the first gas region comprising a first organic vapor, the first organic vapor comprising a first organic fluid in vapor form, the first organic vapor being present in at least a portion of the first gas region at a concentration greater than the UEL; (d) a second gas region, the second gas region comprising a second organic vapor, the second organic vapor comprising the first organic fluid in vapor form, the second organic vapor being present in the second gas region at a concentration less than the LEL; and (e) devices for stretching the cooled cast sheet, wherein at least some of the stretching devices are positioned in the second gas region.
[0127] In a further detailed feature of the invention, the first gas region is enclosed in the housing.
[0128] In a further detailed feature of the invention, the first gas zone includes a plurality of chilled casting rolls arranged in an S-wrap casting configuration.
[0129] In a further detailed feature of the invention, the first gas zone includes one or more rollers arranged in a U-wrap casting configuration.
[0130] Other objects and aspects, features and advantages of the present invention will be set forth in part in the following description, and in part will be apparent from the description or can be learned by the practice of the present invention. In the description, reference is made to the accompanying drawings, which form part of the description and in which various embodiments for practicing the present invention are shown by way of example. The embodiments will be described in sufficient detail to enable those skilled in the art to practice the present invention, and it will be understood that other embodiments may be utilized, and structural changes may be made without departing from the scope of the present invention. Therefore, the following detailed description will not be made in a limiting sense, and the scope of the present invention is best defined by the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0131] The accompanying drawings, which are hereby incorporated into and constitute a part of this specification, illustrate various embodiments of the present invention and, together with the description, serve to explain the principles of the present invention. In the accompanying drawings, wherein like reference numerals represent like parts:
[0132] Figure 1 is a schematic cross-sectional view of one embodiment of an electrochemical cell according to the present invention.
[0133] Figure 2 is a schematic side view of one embodiment of a system for making a microporous sheet product according to the present invention, the system comprising an S-type roll casting configuration;
[0134] Figure 3 yes Figure 2 A schematic side view of a first alternative casting configuration is shown.
[0135] Figure 4 yes Figure 2 Schematic side view of a second alternative casting configuration to the shown casting configuration.
[0136] Figure 5 yes Figure 2 Schematic side view of a third alternative casting configuration to the shown casting configuration. DETAILED DESCRIPTION
[0137] The present invention relates to a microporous sheet product, the use of the microporous sheet product as a battery separator, a battery cell including a battery separator, and a method and system for making the microporous sheet product.
[0138] The present inventors have unexpectedly discovered that by using specific starting materials and / or specific manufacturing methods, the details of which are described more fully below, unique microporous sheet products having desirable properties (which may include, for example, a uniform open porous surface) can be formed. In many cases, the methods of manufacturing the subject microporous sheet products can be achieved at low manufacturing costs and in an environmentally desirable manner.
[0139] As discussed above, one common problem in lithium-ion batteries is that the conductive salt LiPF6 may react with water in the battery electrolyte in a hydrolysis reaction to produce unwanted substances such as lithium hydroxide, hydrogen gas and / or hydrofluoric acid. The production of these unwanted products is undesirable because they may reduce battery performance and battery life, as well as being a health hazard if they leak into the environment.
[0140] Therefore, a first aspect of the present invention is to incorporate a component into the microporous sheet product that can easily minimize the extent of the above-mentioned hydrolysis reaction with LiPF6, and in doing so, can easily minimize the production of unwanted products (such as lithium hydroxide, hydrogen and hydrofluoric acid) that may result from the hydrolysis reaction. According to one aspect of the present invention, this can be achieved by incorporating a condensation polymer into the microporous sheet product, wherein the condensation polymer (rather than LiPF6) can preferentially undergo hydrolysis, thereby minimizing the above-mentioned problems associated with the undesirable production of unwanted products (such as lithium hydroxide, hydrogen and / or hydrofluoric acid). A non-limiting example of such a condensation polymer can be a polyamide. Polyamides can be produced by dehydration reactions between monomers (i.e., dicarboxylic acids and diamines), or by amino acids or their lactams, wherein water is a by-product of such reactions. The connection of monomer molecules in polyamides typically occurs by forming amide groups. The reverse process of this polymerization reaction is hydrolysis, wherein the polyamide can act as a scavenger and react with water or acid. Therefore, by incorporating such polymers into separators of lithium-ion batteries, such polymers can scavenge water or acid from the battery, thereby minimizing battery degradation and extending battery cycle life. The acid can also act as a catalyst for the chain scission rehydration reaction to catalyze the hydration or hydrolysis of the scavenger polymer with water.
[0141] The second aspect of the present invention is a novel method and system for manufacturing microporous sheet products. In at least some embodiments, the microporous sheet product can be composed of a polymerized composition or can include a polymerized composition, the polymerized composition is preferably a polyolefin composition, and the microporous sheet product can have two main surfaces and a thickness between them. In at least some embodiments, the microporous sheet product can be formed by extruding or molding a mixture consisting of or including the following-as an initial molding material: (i) a medium molecular weight polymer with at least 30% crystallinity, preferably a polyolefin, and (ii) based on the total weight of the mixture, 10 to 60 weight % of an organic fluid, the organic fluid having a boiling point of about 135 to 300 ° C and a vapor pressure of about 1 to 50 mm Hg at 70 ° C, and wherein the polymer is at least partially soluble. The mixture can be formed by blending polymers and fluids at an elevated temperature. When the initial molding material is formed (for example, the mixture is extruded through the slit die head of an extruder), the molding material or cast sheet can be in contact with a specific type of vapor region, wherein the cast sheet can stay while cooling and inducing phase separation. The shaped material or cast sheet may be further cooled by a cooling medium on chilled casting rolls or in a cooling bath.
[0142] In at least some embodiments, the aforementioned vapor region may be maintained with vapor of an organic fluid above the upper explosion limit (UEL). This maintenance of the organic fluid vapor above the upper explosion limit can improve the compatibility of the casting sheet surface with the cooling medium (steam and fluid), can promote the phase separation of different fluids and polymers (liquids and solids), thereby resulting in an increased opening-unit pore growth rate of the casting sheet. The contact between the molten casting sheet and the incompatible vapor or fluid may cause the fluid to be partially encapsulated by the polymer. This may result in small, tortuous or closed-unit pores, which may correspond to the sheet surface that may be sealed, thereby showing poor electrolyte penetration (wet-out). In at least some embodiments, the cooling vapor and fluid may be maintained at a temperature below 160°C, and may contain substantially the same organic fluid, which is used to form an initial mixture of polymer and fluid for a residence time sufficient to solidify the molding material. After the molding material leaves the cooling region of the gas above the upper explosion limit, the molding material can be further processed. More specifically, in at least some embodiments, after the cooling region, the subsequent steps can be maintained in an environment below the lower explosion limit (LEL) of the fluid.
[0143] The cooled shaped sheet material may then be subjected to a two-step stretching / fluid evaporation of the sheet and a defined amount of fluid removed from the shaped material. In the first stretching / fluid evaporation step, the initial shaped material may be stretched at least in the machine direction. The first stretched shaped material may then be subjected to a separate second stretching / evaporation step of stretching in the transverse direction (and optionally in the machine direction). The resulting second stretched shaped material may be subjected to a specified high temperature annealing for a period of time under machine or transverse tension to produce the desired resulting sheet product. The sheet product may optionally be relaxed in one or both stretching directions and stored to further improve dimensional stability.
[0144] Microporous sheet products comprising the above-UEL and / or formed under the above-LEL conditions exhibit improved performance as battery separators and may also be used in lithium-based battery cells as well as other types of battery cells.
[0145] The microporous sheet product of the present invention is preferably a highly porous monolithic article suitable for use as an improved battery separator. The microporous sheet product can be considered to have two major surfaces with a thickness therebetween. The thickness can consist of or include a series of alternating first and second interconnected layers (strata) extending substantially in the same direction as the major surfaces of the sheet product. Although the thickness of the microporous sheet product of the present invention can consist of multiple layers, each layer is preferably bonded to the adjacent layer(s) at the layer interface boundary by connecting polymeric elements to achieve a monolithic structure.
[0146] For the sake of clarity, certain terms used to describe the present invention herein and in the appended claims may be defined as follows:
[0147] The term "cast sheet" may define a unitary article having two large surfaces relative to its length and width dimensions and having a thickness between the surfaces. Generally, the term may be used to describe a molten sheet from the time it leaves the extrusion die until the sheet is cooled and solidified into a solid and before the sheet is stretched.
[0148] The term "sheet material" may define a unitary article having two large surfaces relative to its length and width dimensions and having a thickness between the surfaces. In general, the term may be used to describe the structure produced during the initial extrusion or shaping of the material into sheet form, as well as the structure of the material produced during any of the intermediate steps taught to form the final sheet product.
[0149] The term "sheet product" may define a single resulting article having two major or major surfaces relative to its length and width dimensions and having a thickness between the surfaces. The thickness of the resulting article may consist of or include a series of connected open holes from one surface to a second surface. The thickness of the sheet product may be about 0.1 to 10 mils (about 0.0025 to 0.25 mm).
[0150] The terms "layer" or "zone" may be used interchangeably to define different portions of the thickness of a single sheet product that extend in substantially the same length and width directions as the major surfaces, albeit in a somewhat tortuous manner. Thus, a layer may be positioned in a substantially parallel relationship to the major surfaces of the sheet product. Each layer or zone may be formed, merged or interrupted within the sheet product structure.
[0151] The term "first" may be used to modify terms referring to a layer or zone having an average pore size of about 0.001 to 10 microns, preferably about 0.005 to 1 micron, more preferably about 0.01 to 0.5 microns, and having an average pore size that is smaller than the average pore size of the alternating layers adjacent thereto. The term "first" may also be used to modify and refer to the liquid to be mixed with the sheet material and to form the sheet material during the initial process steps of the multi-step stretching / fluid evaporation of the sheet material and the initial extrusion or forming of the sheet material. In addition, as further discussed below, the term "first" may also be used to modify and refer to one or more polymers used to form the sheet product of the present invention.
[0152] The term "second" may be used to modify terms referring to a continuous or discontinuous porous layer or zone having an average pore size of at least 1 micron, preferably 5 microns up to about 100 microns or more (associated with larger pore sizes) and having an average pore size greater than the average pore size of the alternating layers adjacent thereto. The term "second" may also be used to modify and refer to the second process step of a multi-step stretching / fluid evaporation of a sheet material after it has initially been formed, as well as to distinguish the sheet material formed by the second stretching / fluid evaporation step. In addition, as further discussed below, the term "second" may also be used to modify and refer to one or more polymers used to form the sheet product of the present invention.
[0153] The terms "fluid", "liquid" and "solvent", which may be used interchangeably, may refer to the liquid component used to form the initial polymer / fluid mixture to form the sheet material. These terms may also be used to refer to the liquid used to form the cooling fluid, or the medium on the surface of the chilled casting roll, or the cooling bath used to initially cool the formed cast sheet, or the process fluid used in other steps to form the subject sheet product, or the fluid removed by each of the stretching / fluid evaporation steps.
[0154] The terms "gas" and "vapor" which may be used interchangeably may refer to the gas components used in the initial contact medium of the extruded cast sheet. These terms may also refer to the gas composition used to form the above UEL processing region of the subject sheet material and / or the below LEL processing region of the subject sheet material.
[0155] The term "major surface" may refer to the outer surface of the sheet product and the layers adjacent to the major surface.The first layer (exposed side) may form each of the major surfaces of the sheet product.
[0156] The term "separator" may refer to a component of a battery, particularly a storage battery, that can maintain separation between adjacent electrode plates or elements of opposite polarity. The separator may have a variety of configurations, such as a flat, ribbed, or corrugated sheet, which may be in the form of a film or envelope capable of maintaining separation between adjacent electrodes. The separator of the present invention may have a thickness of about 0.1 to 10 mils (about 0.0025 to 0.25 mm), but the exact thickness will be based on its intended battery design.
[0157] The term "crystallinity" may refer to the regular or structured orientation of polymer molecules relative to each other within a polymer block, as opposed to the random, irregular orientation of polymer molecules within a polymer block. The crystallinity of a polymer block may be determined in a known manner by conventional x-ray diffraction analysis.
[0158] The term "UEL" may refer to an Upper Explosion Limit or Upper Explosive Limit, which may be the highest concentration (percentage) of a gas or vapor in air that can produce a flash of fire in the presence of an ignition source (e.g., an arch, flame, heat). The UEL is sometimes also referred to as an upper flammable limit or UFL. Vapor concentrations above the UEL may be considered "too rich" to burn, and may be referred to herein as "above the UEL." A space, volume, or enclosure in which a gas or vapor exists at a concentration above the UEL may be referred to herein as an above-UEL zone.
[0159] The term "LEL" may refer to the Lower Explosion Limit or Lower Explosive Limit, which may be the lowest concentration (percentage) of a gas or vapor in air that can produce a flash of fire in the presence of an ignition source (e.g., furnace arch, flame, heat). Vapor concentrations below the UEL may be considered to not have enough hydrocarbon fuel to burn, and may be referred to herein as "below the UEL." A space, volume, or enclosure in which a gas or vapor exists at a concentration below the UEL may be referred to herein as a below-UEL zone.
[0160] The term "fluid reservoir" may refer to a pool of cooling fluid trapped at the contact point between the cast sheet and the cooling surface of the casting roll. This cooling fluid may increase the thermal conductivity of the sheet and may be formed by condensation of the same extrusion fluid vapor that accumulates over time onto the casting roll surface.
[0161] The term "first polymer" may refer to a polyolefin polymer having an open cell porous network continuous from surface to surface of a sheet product.
[0162] The term "second polymer" may refer to a condensation polymer melted and mixed within the first polymer network, which has a shape after melt recrystallization, which may be in the form of fibrils or particles having length and width. The second polymer may be surrounded by the first polymer and may be discontinuous from surface to surface of the sheet product.
[0163] Material Specifications
[0164] According to one aspect of the present invention, there is provided a microporous sheet product suitable for use as a battery separator, the microporous sheet product being prepared by the following method, the method comprising (a) melt extruding an extrusion mixture to form a sheet material, the extrusion mixture being composed of or comprising (i) a first polymer, (ii) a second polymer, and (iii) a compatibilizing agent, wherein the second polymer can be used as a condensation polymer to remove water or acid in, for example, a lithium-based battery, thereby minimizing undesirable hydrolysis in the lithium-based units of a lithium conductive salt such as LiPF6, wherein the compatibilizing agent can promote mixing of the first polymer and the second polymer, thereby forming micropores in the sheet material; and (b) then, cooling the sheet material.
[0165] The polymer that can be used as the first polymer in the present invention can include one or more types of thermoplastic polymers that are suitable for forming microporous sheets by melt extrusion. Such thermoplastic polymers can have a crystallinity of at least 30%, and preferably at least 40%, wherein it is particularly preferred that the thermoplastic polymer has a crystallinity of about 50% to 90%.
[0166] The preferred first polymer of the present invention may include one or more polyolefins. In particular, the one or more polyolefins of the present invention may include one or more homopolymers, copolymers (i.e., dimer) and / or terpolymers. More specifically, the first polymer may include polyethylene, polypropylene, ethylene-butene copolymers, ethylene-hexene copolymers, and the like, and mixtures thereof. Particularly preferred first polymers may include polyethylene and / or polypropylene homopolymers, and copolymers of these polymers, with small amounts of up to about 10% by weight, preferably about 1 to 10% by weight, of other alpha-olefins (C3-C 10α-olefins) as comonomer units, such as propylene, 1-butene, 1-hexene, etc., and mixtures thereof preferably produced by polymerization using a single-site catalyst. The aforementioned polyethylene can be selected from high-density polyethylene, medium-density polyethylene, branched low-density polyethylene and linear low-density polyethylene.
[0167] The first polymer may be selected from one or more polymers having an average molecular weight of about 100,000 to 10,000,000 Da, with medium molecular weight polymers of about 200,000 to less than about 5,000,000 Da being preferred.
[0168] Melt flow index or MFI is a measure of the ease with which a melt of a thermoplastic polymer flows. MFI is defined as the mass flow rate of a polymer in grams flowing through a capillary of a specific diameter and length in ten minutes via a specified, optional gravity-applied pressure for an optional specified temperature. Methods for determining MFI are described in ASTM D1238 and ISO 1133. Melt flow rate is an indirect measure of polymer molecular weight. The MF of a polymer having a molecular weight higher than 1,000,000 Da is approximately 0. The melt flow index (MFI) of a preferred first polymer may be less than about 0.8, and more preferably in the range of 0 to 0.1.
[0169] The first polymer may constitute from about 10 to 60 weight percent of the initial extrusion mixture.
[0170] The second polymer of the present invention, which is sometimes also referred to herein as a condensation polymer, can be one or more polymers selected from polyamides, polyethers, polyesters, polyoxyethylenes, polyethylene glycols, polypropylene glycols, polycarbonates, polyanhydrides, polyimides, polybenzimidazoles, polyacetals, polysulfones, polyphenylene oxides, polyurethanes, and other polymers produced by dehydration polymerization. The first polymer and the second polymer can be blended with different percentages or different molecular weight materials of such polymers to form an initial sheet material and ultimately form a single sheet product. The preferred condensation polymer can be a copolymer, more preferably a terpolymer, wherein the condensation polymer is generally more amorphous than the first polymer and can be used to improve the partition puncture strength. Even more preferably, the condensation polymer can be a mixture of two or more polymers, at least one of the two or more polymers being a copolymer, wherein the initial weight ratio of the copolymer to the total condensation polymer is about 0.1: 1 to 0.9: 1, more preferably about 0.2: 1 to 0.85: 1, and even more preferably about 0.3: 1 to 0.8: 1.
[0171] When polyamide is used as the second polymer, the polyamide can be named based on the specific chain length of a linear (aliphatic) or aromatic monomer, wherein the amide bond is generated by an amine lactam group and a carboxylic acid group. For example, an aliphatic polyamide with 6 carbon chains can be named polyamide 6. The longer the carbon chain of the polyamide, the greater the improvement in molecular compatibility with polyolefins in the nanocomposite tends to be. Preferably, the polyamide can have a carbon chain of at least 6 carbons, more preferably at least 9 carbons, even more preferably at least 10 carbons, and even more preferably at least 12 carbons. The polyamide can include one or more homopolymers, such as polyamide 9, polyamide 11, polyamide 12 and polyamide 13, one or more copolymers, such as polyamide 10 / 10, polyamide 6 / 9, polyamide 6 / 10, polyamide 6 / 12, and polyamide 13 / 13, or one or more terpolymers, such as polyamide 66 / 6 / 12, or a mixture of homopolymers, copolymers and / or terpolymers. When one or more polyamides are used as the second polymer, the relative viscosity, measured as the ratio of the viscosity of the second polymer to the viscosity of m-cresol, is preferably at least 1.4: 1, more preferably at least 1.7: 1, and even more preferably at least 1.9: 1. The baseline viscosity of m-cresol is 184 cP at 20° C. The viscosity of the polyamide can be measured by dissolving 0.5% of the polyamide in m-cresol.
[0172] The average initial molecular weight of the condensation polymer may be at least 8,000 Da, more preferably at least 12,000 Da, even more preferably at least 20,000 Da, and even more preferably at least 29,000 Da. When the microporous sheet product of the present invention is exposed to water, such as may occur when the microporous sheet product is used as a separator in a battery, a reversal of the polymerization dehydration reaction may occur to some extent. In turn, this reversal may result in a decrease in the average molecular weight and viscosity of the second polymer of the microporous sheet product. The extent of the reduction in the molecular weight of the second polymer caused by this reversal may depend on the percentage of water and the second polymer present in the battery. For example, after water exposure, the ratio of the average initial molecular weight of the second polymer to the average final molecular weight of the second polymer may be in the range of 1:1 to 1000:1. More preferably, the reduction in the average molecular weight of the second polymer may be between about 90% and about 20% of the pre-extrusion (or initial) molecular weight of the second polymer. It is understood that an extreme reduction in the molecular weight of the second polymer is undesirable because very low molecular weight second polymers may tend to migrate from the microporous sheet product matrix into the electrolyte. Therefore, when the microporous sheet product is used as a separator, some minimum entanglement of the second polymer with the microporous sheet product matrix is desirable in order to maintain the integrity of the microporous sheet product and prevent dendrite shorting. e) is generally defined as polymer chains that cross any plane three times and can therefore be considered entangled. The minimum entanglement (M) for various polymers is provided below. e ) value examples:
[0173]
[0174] The second polymer minimum entanglement molecular weight can be specified as at least 1000 Da, preferably at least 2000 Da, more preferably at least 3000 Da, and even more preferably at least 4000 Da. In order to obtain such minimal entanglement within the unit, the final second polymer molecular weight depends on the starting second polymer MW and the amount of water present. The second polymer of the present invention typically has an initial polymer molecular weight and a final polymer molecular weight (e.g., after exposure to H2O, HF or LiPF6, resulting in a hydrolytic cleavage reaction of the second polymer). The ratio of the reduction of the initial and final polymer MW due to the hydrolytic cleavage can be expressed as R c For example, in the case of polyamide 6, which typically has a monomer molecular weight of 341 Da, and water, which typically has a molecular weight of 18 Da, the amount of initial second polymer and water that can be present in a cell (e.g., a battery) while still maintaining the final minimal polymer entanglement can be approximated as follows:
[0175] [(W (ip) / M (ip) )+(W (w) / M (w) )] / [W (ip) / M (ip) ]=R c
[0176] R c =[M (ip) / M (fp) ]
[0177] W (ip) / W (w) =M (ip) / [18*(R c -1)]
[0178] R c = Second polymer decomposition rate
[0179] W (ip) = the initial total weight of the second polymer introduced into the unit
[0180] W (w) = Total weight of water in the unit
[0181] M (m) = specific molecular weight of monomer
[0182] M (ip)= Average initial molecular weight of the second polymer
[0183] M (fp) = the average final molecular weight of the second polymer after hydrolytic cleavage, or the minimum entanglement molecular weight
[0184] When defining a target R for a given second polymer c When the initial second polymer weight is , the amount of the initial second polymer required to limit excessive cleavage of water in the unit can be estimated. The approximate ratio of the initial second polymer weight to the initial water weight [W (ip) / W (w) ] is preferably at least 10:1, more preferably at least 50:1, even more preferably at least 100:1, and still even more preferably at least 500:1, wherein the ratio is preferably increased to a maximum of about 5,000:1. Minimum lysis rate R c It may be at least 1.1, but is preferably less than about 1,000.
[0185] When polyoxyethylene or polypropylene glycol is used as the second polymer, the initial molecular weight of the polyoxyethylene or polypropylene glycol is preferably at least 110,000 Da, more preferably at least 310,000 Da, even more preferably at least 910,000 Da, and even more preferably at least 2,100,000 Da. In practically all cases, it is preferred to use a second polymer having a higher molecular weight; at the same time, in almost all cases, the average initial molecular weight ratio of the second polymer to the first polymer may be lower than about 2:1, preferably lower than about 1:1, more preferably lower than about 0.5:1, and even more preferably lower than about 0.2:1, however preferably higher than about 0.01:1. When polyamide and polyoxyethylene are used in the form of a mixture, the weight ratio of polyamide to polyoxyethylene is preferably higher than about 0.1:1, and preferably lower than about 10:1, more preferably lower than about 7:1, and even more preferably lower than about 3:1.
[0186] Since polyamide is the product of condensation or dehydration polymerization, the reaction is reversible when water and acid (such as hydrofluoric acid) are present. More specifically, in the presence of acid and water, polyamide can be converted back to its monomer and / or lower molecular weight oligomer. Due to the above-mentioned reaction of polyamide with water, there is less water available in the lithium cell containing LiPF6 to react with LiPF6 to form unwanted products such as lithium hydroxide, hydrogen and hydrofluoric acid. As mentioned above, hydrofluoric acid can cause degradation and shortened life of lithium-ion batteries and other energy storage devices using fluorine-containing organic electrolytes. Even a small amount of residual moisture (introduced during battery production) can lead to the formation of highly corrosive hydrofluoric acid in such battery cells. This can affect the chemical properties of the electrolyte, resulting in performance degradation, device failure, or in the worst case, degassing and leakage of the electrolyte. The hydration of the second polymer produces functional groups of amines, alcohols and carboxylic acids, and reduces the molecular weight of the second polymer. The hydration of polyoxyethylene will produce functional end groups of diols. When the hydroxyl groups of water cleave the polycondensate according to the present invention, the resulting functional groups tend to improve the wettability of the separator and the electrolyte retention, and thus tend to improve the cell cycle life.
[0187] Separators having a high concentration of the second polymer compared to the first polymer will often decompose and break down in lithium-based batteries, resulting in dendrite shorting. The second polymer preferably constitutes about 0.1 to 20 weight percent of the initial extrusion mixture, more preferably about 1 to 15 weight percent, and even more preferably about 2.1 to 9.9 weight percent. The initial weight ratio of the second polymer to the first polymer is preferably about 0.01:1 to 1:1, more preferably about 0.02:1 to 0.5:1, even more preferably about 0.05:1 to 0.3:1, and even more preferably about 0.1:1 to 0.2:1. Due to the potential hydrolysis reaction of the second polymer in the lithium battery, the second polymer preferably forms a discontinuous phase of the microporous sheet product and the first polymer forms a continuous porous network of the microporous sheet product, wherein the first polymer preferably forms connecting fibrils constituting the continuous porous network.
[0188] Due to the scavenging effect of the second polymer on water, this scavenging effect can be utilized, for example, when the microporous sheet product is used as a battery separator in a lithium-based cell, the benefit of the second polymer can be best demonstrated when greater than about 10 ppm of water is available, more so when greater than about 40 ppm of water is available, and even more so when greater than 150 ppm of water is available. During the cell cycle life, moisture always enters the lithium-based cell. However, excessive moisture in the battery separator also destroys the effect of the scavenging polymer, especially in the cell assembly environment with high relative humidity. Therefore, because some of these condensation polymers are hygroscopic, the separator may need to be dried, for example, by heating or vacuuming before adding the lithium electrolyte. The moisture in the separator is preferably less than about 1% or 10,000 ppm, more preferably less than about 2000 ppm, even more preferably less than about 900 ppm, and still more preferably less than about 300 ppm. Prior to battery assembly, the separator is preferably packaged in a sealed package, such as an aluminum foil bag and a vacuum package.
[0189] A compatibilizing agent (also sometimes referred to herein as a "first fluid") may be included in the extrusion mixture to facilitate the formation of an initial sheet material. The first fluid may be selected from an organic fluid that can provide at least a slight solubility relative to the first polymer and the second polymer. Thus, the first fluid may serve as a sufficient solvent for the first polymer and the second polymer to allow the first polymer and the second polymer and the first fluid to form a uniform mixture having fluidity at an elevated temperature (e.g., about 100 to 250°C), so that an initial sheet material may be formed therefrom. The first fluid may contain one or more hydrocarbon oils (e.g., mineral oil), or may contain one or more organic esters or phthalates. Preferably, the first fluid is selected from low molecular weight, high vapor pressure organic liquids (e.g., mineral spirits, relatively low molecular weight alkanes, C9 to C 20Aliphatic hydrocarbons, alicyclic hydrocarbons or aromatic hydrocarbons (such as nonane, decane, p-xylene, undecane, dodecane, and octadecane to eicosane and the like), and mixtures thereof). The first fluid preferably has a high vapor pressure, for example, about 1 to 50 mm Hg at 70°C (e.g., about 1 to 5 mm Hg at 70°C, about 5 to 10 mm Hg at 70°C, about 10 to 20 mm Hg at 70°C, about 20 to 40 mm Hg at 70°C), and preferably has a vapor pressure of about 0.1 to 5 mm Hg at 20°C. The first fluid preferably has a boiling point of about 135 to 300°C (about 275 to 572°F), particularly preferably a boiling point of about 170 to 250°C (about 338 to 482°F). Preferably, the first fluid comprises a fluid mixture having a boiling range (initial to final boiling point) that is at least 10° C. wide, more preferably at least 15° C. wide, and even more preferably at least 20° C. wide, thereby enhancing the ability to provide controlled multiple temperatures and multiple steps of solvent evaporation. In certain product applications, low volatility hydrocarbons or mineral oils may be used. Preferably, the first fluid comprises about 20 to 85% by weight of the extrusion mixture, more preferably about 30 to 80% by weight of the extrusion mixture, and even more preferably about 40 to 75% by weight of the extrusion mixture.
[0190] To promote melt homogeneity between the first polymer and the second polymer, particularly where the first polymer is a polyolefin, the second polymer preferably has a T of less than about 240°C. m (melt temperature), more preferably less than about 200°C, and even more preferably less than about 160°C. When the sheet material comprising the first polymer and the second polymer leaves the extrusion die, the second polymer preferably crystallizes before the first polymer, forming crystal seeds and promoting crystallization and formation of the entire polymer matrix. In a preferred embodiment, the extrusion mixture comprising the first polymer and the second polymer can be melt extruded to form a molten sheet. The molten sheet can then be exposed to a vapor region above the UEL (which is further discussed below) to accelerate crystallization of the first polymer by inoculation of the second polymer. In addition, the second polymer and the UEL fluid vapor preferably have a solubility parameter difference greater than 1, more preferably greater than 2. The solubility parameters (in cal) of various components that may be present in connection with the present invention are listed below. 1 / 2 / cm 3 / 2 ):
[0191]
[0192]
[0193] The microporous sheet product of the present invention can be composed of a single layer of any type described in this document, or can include a plurality of stacked or laminated layers, one or more of which can be any of the types described in this document. Laminated structures can be easily formed using conventional multi-sheet extrusion head devices (e.g., coextrusion) or by laminating two or more previously formed layers together using heat, adhesives, or other devices. The example of multilayer structure is described in European Patent Application Publication No. EP 1911352 A1, published on April 16, 2008, which is incorporated herein by reference. One or more layers of the multilayer structure can be a protective layer. The materials used in each layer should be fully compatible and miscible to allow bonding during extrusion and juxtaposition of the layers.
[0194] When the laminated structure is used as a battery separator in a lithium battery, the layer containing the second polymer is preferably not in direct contact with the lithium positive electrode. When a laminated structure of three or more layers is used, the layer containing the second polymer is preferably present only in the inner layer or core layer. For example, in an ABA type laminated structure, the outer layer or A layer may not have a second polymer, and the core layer or B layer may contain a matrix of a first polymer (which may be a polyolefin) and a second polymer. On the other hand, when each layer of the laminated structure contains a second polymer, the core layer or inner layer preferably has a second polymer to first polymer ratio higher than the outer layer, and the ratio is at least 1.5 times higher in the core layer or inner layer than in the outer layer, more preferably 3 times higher in the core layer or inner layer than in the outer layer, and even more preferably 5 times higher in the core layer or inner layer than in the outer layer. Layers with lower amounts of the second polymer may tend to provide strength to the laminated structure, and layers with larger amounts of the second polymer may tend to have larger pore sizes and higher porosity in the laminated structure.
[0195] In the laminated coextruded structure of the present invention, some or all of the layers of the structure can be prepared using extrusion mixtures containing different fluid percentages. For example, the surface or outer layer of the structure can have a higher fluid percentage than the center layer or core layer, and this higher fluid percentage can be at least 2% higher, more preferably at least 4% higher, even more preferably at least 7% higher, and even more preferably at least 11% higher. A higher surface fluid percentage can accelerate extrusion phase separation during cooling, and can make larger pore sizes and higher porosity possible in the surface layer of the structure.
[0196] In the laminated co-extruded structure of the present invention, some or all layers of the structure can be prepared using extrusion mixtures with different polymer average molecular weights. For example, the surface layer can have a lower polymer average molecular weight than the core layer, and this lower polymer average molecular weight can be at least 10,000Da lower than the polymer average molecular weight of the core layer, preferably at least 20,000Da lower than the polymer average molecular weight of the core layer, more preferably at least 50,000Da lower than the polymer average molecular weight of the core layer, and even more preferably at least 100,000Da lower than the polymer average molecular weight of the core layer. The lower average molecular weight of the polymer mixture can accelerate the extrusion phase separation during cooling, and can make larger pore sizes and higher porosity possible in the surface layer of the structure.
[0197] Certain applications may benefit from or may require a polymer coating solution applied to a separator or electrode, in which a low crystalline polymer (such as cyclic olefins, styrene, butylene and isobutylene) may be incorporated. The polymerized composition may further include fillers, colorants, antioxidants, stabilizers and the like. Although solid particulate materials are not a desired component of the initial polymer composition forming the sheet material and the resulting sheet product, when they are present, they should be limited to less than about 20% by weight of the polymerized composition for forming the initial polymerized sheet material as described herein, preferably less than about 5% by weight. The remaining description of the present invention can be illustrated by using the polyolefins forming the present sheet product and the separators made therefrom.
[0198] Using Microporous Sheet Products as Battery Separators
[0199] Reference now Figure 1 , shows a schematic cross-sectional view of one embodiment of an electrochemical cell constructed according to the teachings of the present invention, which is generally indicated by reference numeral 11. For clarity, simplicity and / or ease of illustration, certain details of the electrochemical cell 11 discussed elsewhere in this application or not important to understanding the present invention may be omitted from this description and / or may be included from Figure 1 may be omitted or may be shown therein in a simplified manner.
[0200] The electrochemical cell 11 , which may be a battery cell and preferably a lithium-ion battery cell, may include an anode 13 , a cathode 15 , an electrolyte 17 , a separator 19 , and a housing 21 .
[0201] Anode 13 , which may be, for example, an anode of the type commonly found in lithium-ion battery cells, may include an electrode composed of or containing carbon (eg, graphite).
[0202] Cathode 15 , which may be, for example, a cathode of the type commonly found in lithium-ion battery cells, may include an electrode consisting of or containing a metal oxide such as LiCoO 2 or LiMn 2 O 4 .
[0203] The electrolyte 17, which may be, for example, an electrolyte of the type commonly found in lithium-ion battery cells, may include one or more liquid organic solvents in which one or more lithium salts are dissolved. The one or more liquid organic solvents may include one or more organic carbonates, such as ethylene carbonate and diethyl carbonate. The lithium salt may include lithium hexafluorophosphate (LiPF6).
[0204] The separator 19 may be a microporous sheet product of the type described above including a condensation polymer.
[0205] Housing 21 may be of a type commonly found in lithium-ion battery cells, for example, and is preferably constructed to contain anode 13, cathode 15, electrolyte 17, and separator 19. Housing 21 is preferably constructed in such a way as to be substantially impermeable to the ingress or egress of water.
[0206] As described above, the presence of water in the electrochemical cell 11 can lead to the production of some potentially undesirable substances. Therefore, the presence of water in the electrochemical cell 11 is generally considered to be undesirable. Nevertheless, despite the fact that the presence of water in the electrochemical cell 11 is generally undesirable, some water may be present in the electrochemical cell 11. This water may be present in the electrochemical cell 11, for example, during cell assembly, or may become trapped in one or more of the components of the electrochemical cell 11. Fortunately, due to the presence of condensation polymers in the separator 19, the condensation polymers can be used to remove water from the cell, and the potential harmful effects of this water can be minimized. On the other hand, due to its reaction with water, excessive depolymerization of the condensation polymer is undesirable because excessive depolymerization can cause the condensation polymer to leach or migrate from the separator 19, potentially resulting in significant changes in the physical (or other) properties of the separator 19. According to the present invention, W ip / W w (i.e., the ratio of the initial total weight of polycondensates present in the electrochemical cell 11 to the initial total weight of water present in the electrochemical cell 11 (the above initial total weight of water preferably refers to the amount of water present in the electrochemical cell 11 immediately after any drying step (such as vacuum drying) that has been carried out during or before the cell is manufactured)) is preferably at least 10:1, more preferably at least 50:1, even more preferably at least 100:1, and even more preferably at least 500:1, wherein the ratio is preferably a maximum of about 5,000:1. As mentioned above, the initial total weight of water present in the electrochemical cell 11 can be greater than 10 ppm, and can even be greater than 40 ppm. Alternatively, the polycondensate cracking rate Rc The molecular weight ratio (ie, the ratio of the average initial molecular weight of the polycondensate to the average final molecular weight (or its minimum entanglement molecular weight) of the polycondensate after hydrolysis) is preferably at least 1.1, but preferably less than about 1,000.
[0207] It should be understood that although Figure 1 A single electrochemical cell 11 is shown, but a plurality of electrochemical cells 11 may be electrically connected to one another and contained within a common housing to form a multi-cell battery.
[0208] It should also be understood that while the electrochemical cell 11 is described herein as preferably a lithium-ion battery, the electrochemical cell 11 is not limited to a lithium-ion cell and may be any type of lithium-based electrochemical cell.
[0209] Process Description
[0210] According to another aspect of the present invention, a novel method for making a microporous sheet product is provided. In one embodiment, the method may include the following steps: (i) melt extruding the extrusion mixture to form a cast sheet; (ii) cooling the cast sheet in a first gas zone, the first gas zone containing vapor of an organic fluid, the vapor being present in at least a portion of the first gas zone at a concentration above the UEL; and (iii) performing at least some stretching on the cooled cast sheet in a second gas zone, wherein the vapor of the organic fluid is at a concentration below the LEL in the second gas zone.
[0211] More specifically, in at least some embodiments of the present invention, the first polymer, the first fluid and the optional second polymer can be mixed together to form a substantially uniform composition. Mixing can be performed before or as part of forming the first molding material, such as by feeding the polymer (one or more) and the fluid into a single screw or twin screw feed chamber of an extruder. Such extruders are well known and are exemplified in the following documents, all of which are incorporated herein by reference: U.S. Patent No. 7,887,727 B2, inventors Lee et al., issued on February 15, 2011; U.S. Patent Application Publication No. US2011 / 0133355 A1, inventors Takita et al., published on June 9, 2011; U.S. Patent Application Publication No. US2010 / 0041779 A1, inventors Lee et al., published on February 18, 2010; U.S. Patent Application Publication No. US2007 / 0138682 A1, inventors Lee et al., published on June 21, 2007; PCT International Publication No. WO2009 / 51278 A2, published on April 23, 2009; PCT International Publication No. WO 2007 / 46496 A1, published on April 23, 2009; PCT International Publication No. WO 2007 / 73019A1, published on June 28, 2007; and PCT International Publication No. WO 2008 / 72906A1, published on June 19, 2008.
[0212] Although not particularly critical, uniform melt blending of polymer solutions (wherein the first polymer may be, for example, a polyolefin) may be performed in a double-screw or twin screw extruder. The first fluid may be added to the polymer (one or more) before melt blending begins; alternatively, the first fluid may be supplied to the extruder in an intermediate step of blending. Due to the potential large solubility parameter difference between the first polymer and the second polymer (in those cases where the second polymer is present), the polymer blend may be pre-compounded. In other words, the first polymer and the second polymer may be melted together in a first extruder or compounder of a twin screw extruder, and the molten mixture is then fed to a second extruder of the twin screw extruder to produce a cast sheet. However, in order to minimize the particle size of the second polymer and to achieve nanoparticle compounding, the extruder may have a length to screw diameter ratio (L / D) of at least 30:1, preferably at least 36:1, and more preferably at least 42:1. A high total mechanical energy input is required to melt, molecularly intertwine and overcome the large solubility parameter difference between the first polymer and the second polymer to produce a homogeneous and uniform cast sheet and sheet product. The extruder energy input may be increased by increasing the extruder screw rpm and / or by adding kneading blocks. In doing so, the total melt energy input may be at least 0.15 kwh / kg, preferably at least 0.25 kwh / kg, more preferably at least 0.35 kwh / kg, and even more preferably at least 0.45 kwh / kg.
[0213] The mixture may be heated to a temperature above the melt temperature (T) of the polymer(s) as measured by conventional differential scanning calorimetry (DSC). m ) while being below the boiling temperature of the first fluid. A temperature of about 100°C to about 250°C may be suitable for this purpose, while subjecting the mixture to shear forces to form a uniform mixture of the components before forming (e.g., extruding through a die head) into an initial shaped sheet material. During this operation, the polymer(s) may lose most, if not all, of its(their) crystallinity characteristics.
[0214] The formed mixture can be formed into initial sheet material (that is, cast sheet) by any technology, such as by extruding the mixture through the extrusion of an extrusion die. This formation of initial sheet material can be carried out at an elevated temperature (such as those for mixing fluid with polymer (one or more) as indicated above). The initial sheet material can have a thickness that is enough to allow stretching without causing material splitting. The appropriate thickness of the initial sheet material that can be easily determined by a person of ordinary skill in the art can be about 0.1 to 5mm, preferably about 0.2 to 3mm, more preferably about 0.2 to 2mm.
[0215] Initial sheet material can be cooled by passing sheet from mold and entering the first gas zone.When in the first gas zone, initial sheet material can contact with medium on the surface of cold casting roll or in cooling bath.As discussed further below, the gas present in the first gas zone can include organic fluid vapor and can be mainly the vapor of the first fluid or the vapor of the second fluid.The component of the second fluid and its vapor can be formed by at least 50 % by weight, preferably at least 70 % by weight, more preferably at least 90 % by weight and even more preferably 100 % by weight for forming the same fluid (that is, the first fluid) that is contained in the initial sheet material.As described below, particularly preferably make the first fluid and the second fluid have the same component and also be 100 % by weight single liquid, to help process and be easy to allow the recirculation of fluid.When the second fluid is composed of the first fluid less than 100 % by weight, the remaining fluid is preferably selected from one or more organic fluids, which are miscible with the first fluid and have boiling point, flash point and vapor pressure characteristics in the same range indicated above for the first fluid. The fluid may be maintained at a temperature of up to about 100° C. or by maintaining the surface of the chilled casting roll at below about 100° C. The initially formed sheet material may be retained in the fluid for a time sufficient to reduce the temperature of the sheet material to below the melt temperature (one or more) of the polymer (one or more). The initially formed sheet material may be retained in the fluid for up to about 90 seconds, preferably from about 0.01 to 90 seconds, more preferably from about 0.7 to 50 seconds, and even more preferably from about 1 to 20 seconds. The time is preferably sufficient to cool the initially formed sheet material to below the T of the polymer (one or more) used. m duration.
[0216] The first gas region may be maintained at ambient temperature or at a temperature in the range of about -20 to 160°C. The first gas region temperature is preferably below about 130°C, and more preferably below about 100°C, but preferably above about 30°C. The residence time of the initial sheet material in the first gas region may be short, such as about 0.01 to 20 seconds. The space defining the first gas region may be covered or closed. In at least part of the first gas region, the first organic vapor, which may include the vapor of the first fluid or the vapor of the second fluid, may exist at a condition (i.e., concentration) above the UEL. For example, according to the first embodiment, the first organic vapor may exist at a condition above the UEL throughout the entirety of the first gas region. In other words, according to the first embodiment, the first organic vapor may exist at a condition above the UEL at all locations within the first gas region. It may also be the case that even the concentration of the first organic vapor is not constant between locations within the first gas region. Alternatively, according to the second embodiment, the first organic vapor may exist at a condition above the UEL at one or more locations within the first gas region, but it is not necessary to exist at a condition above the UEL at every location within the first gas region. For example, the first organic vapor may be in above-UEL conditions at one or more locations within the first gas region, and the first organic vapor may not be in above-UEL conditions at one or more other locations within the first gas region. In addition, among those locations within the first gas region where the first organic vapor is in above-UEL conditions, there may be some variation in concentration at different locations, and / or among those locations within the first gas region where the first organic vapor is not in above-UEL conditions, there may be some variation in concentration at different locations. In some, but not all, cases of the second embodiment described above, the average concentration of the first organic vapor throughout the first gas region may be in above-UEL conditions, with some locations of the first gas region being in above-UEL conditions and other locations of the first gas region not being in above-UEL conditions. In some, but not all, cases of the second embodiment described above, the first organic vapor may be in above-UEL conditions at some or all locations within the first gas region through which the sheet material passes (with some of the remaining locations not being in above-UEL conditions for the first organic vapor). For example, the first organic vapor may be present above UEL conditions at all locations within the first gas region through which the sheet material passes, such as a path beginning at an inlet of the enclosure defining the first gas region, extending to any chilled casting rollers within the enclosure, and then terminating at an outlet of the enclosure defining the first gas region. In addition, the first organic vapor may also be present above UEL conditions at locations within the first gas region immediately adjacent to the above path. As another example, the first organic vapor may be present above UEL conditions at only one or more portions of the above path, such as portions of the path beginning at or near the enclosure inlet and extending to the chilled casting rollers (and possibly including the chilled casting rollers).Additionally, the first organic vapor may also be present above UEL conditions at a location within the first gas region proximate to the portion(s) of the pathway.
[0217] When hydrocarbon vapor is used as the first organic vapor in the first gas region at above UEL conditions, the hydrocarbon vapor may be present in at least a portion of the first gas region at a concentration greater than about 3 vol%, preferably greater than about 7 vol%, more preferably greater than about 12 vol%, and even more preferably greater than about 20 vol%. As another example, when mineral spirits vapor is used as the first organic vapor in the first gas region at above UEL conditions, the mineral spirits vapor may be present in at least a portion of the first gas region at a concentration greater than about 5 vol%, preferably greater than about 6 vol%, more preferably greater than about 8 vol%, and even more preferably greater than about 11 vol%. Due to the design of the first gas region enclosure, the first organic vapor accumulated from the extrusion steady state may not be sufficient to replace 100% of the atmospheric air, oxygen, or water that may be present within the enclosure. As a result, the upper limit of the percentage of the first organic vapor in the enclosure may be less than about 60%, more likely less than about 90%, and most likely less than about 99%. In addition, 100% filling of the first organic vapor by a second non-extrusion source may not be economically feasible.
[0218] The above-UEL conditions of the first gas region can maximize the compatibility of cooling, condensation and phase separation of the surface of the cast sheet. In doing so, similar to the compatibility and solubility parameters of the inner core of the sheet, the first gas region can ensure the uniformity of the maximum open surface pores and surface phase separation. The above-UEL conditions of the first organic vapor in the first gas region can also minimize the possibility of combustion in the first gas region. Above-UEL conditions can be created by introducing the first organic vapor or reducing the air flow in the first gas region shell to allow the first organic vapor to accumulate from extrusion. The first gas region shell can be electrically grounded. To further improve safety, an inert gas (such as nitrogen or carbon dioxide) can be used to achieve the above-UEL conditions of the first gas region, and the oxygen concentration can be reduced to less than 21% by volume of the normal atmosphere. The oxygen vapor concentration in the gas region above the UEL or below the LEL is preferably less than about 20%, more preferably less than about 16%, even more preferably less than about 14%, and even more preferably less than 12%. At and below 14% oxygen concentration, the gas region may be considered to be below the limiting oxygen concentration (or LOC) because the fuel (e.g., the first organic vapor) is non-flammable below the LOC regardless of its concentration. Thus, when the first gas region is below the LOC, it may be considered equivalent to and / or included in above-UEL conditions. The ratio of the first organic vapor to oxygen in the above-UEL gas region or in the below-LEL gas region is preferably greater than about 0.1:1, more preferably greater than about 0.5:1, even more preferably greater than about 1:1, and still even more preferably greater than about 2:1.
[0219] As the molten mixture exits the die, the first fluid vapor may evaporate from the cast sheet due to the transition from the extruder pressure (which is relatively high) to the ambient pressure (which is relatively low). When the cast sheet and casting roll environment are properly enclosed and contained, the evaporation of the first fluid from the cast sheet can help create, supply, establish and maintain organic fluid vapor conditions above the UEL. The housing may contain a subcooled vapor section. In order to ensure steady-state accumulation of organic fluid vapor from extrusion, the cast sheet inlet and outlet can be specially designed to limit the outflow of organic fluid vapor or the inflow of air, such as by having an open gap of less than about 50 mm between the cast sheet and the housing to limit the rate at which ambient air enters the housing, preferably less than about 0.1 m 3 / min, more preferably less than about 0.001m 3 In all cases, the potential air inlet volume will be less than the potential vapor volume generated from evaporation of the extruded first fluid.
[0220] In a preferred embodiment, the organic fluid vapor of the first gas region may have a solubility parameter equal to the first fluid or within one solubility parameter unit of the first fluid. Such conditions above the UEL tend to produce more compatible and more uniform open surface porous cast films. In contrast, if a cast sheet is formed under conditions below the UEL, the surface of the sheet product tends to be less uniform and tends to have randomly crystallized polymer patches (patches). By cooling the cast sheet in the region above the UEL, the first fluid vapor can be allowed to cool after extrusion. Preferably, the vapor region is maintained between about 30 and 200°C below the boiling point of the first fluid, resulting in preferential supersaturation of the extruded fluid vapor and condensation onto the surface of the chilled casting roll. The first fluid may become supersaturated at a given temperature and may be deposited on the surface of the chilled roller. This cooled surface fluid can increase the thermal conductivity between the cast sheet and the casting roller, and can accelerate phase separation to achieve the formation of an open pore network, thereby increasing the conductivity of the separator and reducing the tortuosity of the pore matrix. The preferred thermal conductivity may be higher than 0.05W / mK. A typical thermal conductivity coefficient of air to the surface of a chill roll, where the chill roll is made of steel, may be 0.024 W / mK, while an organic cooling fluid may increase the coefficient to 0.137 W / mK, and water may be 0.548 W / mK. Higher thermal conductivities are preferred; however, water has a large solubility parameter difference relative to the cast sheet fluid and may form a nonporous surface layer on the cast sheet.
[0221] In some types of cast sheet cooling configurations, such as the S-type roll casting configuration (see Figure 2 and Figure 3 , which will be discussed further below), the two chilled casting rolls may show a microlayer of condensed fluid on the roll surface. In addition, in the S-type roll-wrapped casting configuration, the two chilled casting rolls preferably do not contact each other to prevent compression of the surface of the cast sheet. The gap between the two rolls may be at least 50 microns, preferably at least 200 microns, and more preferably at least 1,000 microns but less than about 20 mm. When the cast sheet is exposed to fluid vapor under conditions above the UEL, the surface layer thickness may be less than about 20 microns, preferably less than about 10 microns, more preferably less than about 7 microns, and even more preferably less than about 4 microns.
[0222] The initially formed shaped sheet material, when it is produced by an extruder or other shaping device, may comprise polymer(s) and fluid, and although such sheet material may be substantially amorphous, it may still retain the original crystallinity of the residual polymer feed. Upon cooling the initial sheet material, some polymer recrystallization may occur. Thus, the cooled initial sheet material may exhibit a polymer crystallinity of up to about 30 mass %, but more typically less than 20 mass %, such as less than 10 mass %.
[0223] The cast sheet may contact at least one cooling surface, preferably two cooling surfaces, while passing through the first gas zone to further cool both cast sheet surfaces. For example, in an S-type roll casting configuration, the first cast sheet surface may be cooled by the first roll surface, and the second cast sheet surface may be cooled by the second roll surface. In contrast, in a U-type roll casting configuration (see Figure 4 , discussed further below), typically achieves cooling of only one side of the cast sheet surface; therefore, a U-shaped roll casting configuration may produce lower cooling efficiency. When an S-shaped roll casting configuration is used, the roll diameter of the first roll is preferably equal to or smaller than the second roll to cause a shorter first surface cooling residence time. For example, the ratio of the diameter of the first roll to the diameter of the second roll may be less than 0.9:1, preferably less than 0.75:1, more preferably less than 0.5:1, and even more preferably less than 0.33:1. The cast sheet may contact the first roll in the S-shaped roll casting configuration anywhere along the first half of the S-shaped path before the web transfer inflection point (i.e., the point at which the cast sheet transfers from the first roll to the second roll). The cast sheet may leave or be released from the second roll anywhere along the second portion of the S-shaped path after the inflection point. When two cooling rolls are used, the cast sheet preferably has a shorter residence time on the first cooling roll than on the second cooling roll. For example, the residence time on the first cooling roll may be at least 10%, preferably at least 25%, more preferably at least 50%, and even more preferably at least 70% shorter than the residence time on the second cooling roll.
[0224] like Figure 5 As exemplified in FIG. 1 , when two casting rolls are aligned in an imaginary plane P, a specific cast sheet entry angle α measured from the mold melt outlet to the plane P may be between 20 and 85 degrees, more preferably between 30 and 80 degrees, and more preferably between 45 and 80 degrees. Below 20 degrees, the second surface of the cast sheet may cool slowly. Above 85 degrees, the cooling of the first surface may be insufficient, which may cause sheet instability when transferring the sheet from the first roll to the second roll.
[0225] The first fluid vapor from the first gas zone can condense onto the surface of the chill roll, thereby forming a surface layer of fluid condensate on the surface of the chill roll. The cast sheet can then contact this surface layer on the surface of the chill roll. This liquid surface layer on the surface of the chill roll can be desirable because it can increase thermal conductivity in the cooling of the cast sheet. The roll(s) can be maintained at about -20°C and T m -20°C, more preferably about 30°C and T m -40°C, and even more preferably about 50°C and T m-50° C. In the case where the first polymer is polyethylene, the temperature of the chill roll(s) is preferably between about 50° C. and 90° C. Cooling temperatures that are too low may undesirably slow phase separation within the sheet, while cooling temperatures that are too high may not allow vapor from the first gas zone to condense onto the chill roll surface.
[0226] Water may interfere with the phase separation of the polymer mixture. Therefore, the roller temperature can be maintained at a certain temperature to limit the condensation of water vapor thereon. During the time period of high relative humidity (such as during the summer), the desire to limit water condensation may be particularly great. The closure of the first gas region can also be used to limit the entry of water vapor therein. In the first gas region, the water vapor is preferably less than about 30,000 ppm (70% RH, at 38°C), more preferably less than about 21,000 ppm, even more preferably less than about 8,000 ppm, and even more preferably less than about 3,000 ppm. The fluid condensate can cover at least 90% of the casting sheet contact surface, preferably at least 98% of the casting sheet contact surface, and more preferably at least 99.9% of the casting sheet contact surface. The thickness of the fluid condensate on the cooling roller (one or more) is preferably at least 0.01 microns, more preferably at least 0.11 microns, even more preferably at least 2 microns, and even more preferably at least 11 microns but less than about 1 mm. A doctor blade can be used to distribute the fluid on the roller surface. If the second fluid is different from the first fluid, the second fluid may be substantially soluble in the first fluid within a few solubility parameter units. The fluid between the casting roller and the casting sheet may be a vaporizable hydrocarbon. Such a vaporizable hydrocarbon may be an aliphatic hydrocarbon, which may be a C6 to C30 vaporizable hydrocarbon, more preferably a C8 to C20 vaporizable hydrocarbon. Due to the compressive contact between the casting sheet and the casting roller, an accumulation or buildup of cooling liquid, i.e. a fluid cooling reservoir, may occur. The length of this fluid cooling reservoir, which may be deposited on the periphery of the roller in the direction of roller rotation of the sheet, may be at least 0.5 mm, preferably at least 1.1 mm, and more preferably at least 2.1 mm. The thickness of the fluid cooling reservoir between the roller and the sheet may be at least 10% thicker than the above-mentioned fluid condensate, or at least 0.01 mm, and preferably at least 0.11 mm but less than about 2 mm.
[0227] Upon cooling in the manner described above, the formed sheet material then moves from an above-UEL environment in the first gas region to a below-LEL environment or condition in the second gas region. Generally speaking, when hydrocarbons are used as the organic fluid, the hydrocarbon vapors at below-LEL conditions may be less than about 2 volume percent, preferably less than about 1.5 volume percent, and more preferably less than about 0.9 volume percent. As a more specific example, when mineral spirits are used as the organic fluid, the mineral spirits vapors at below-LEL conditions may be less than about 0.7%, preferably less than about 0.6%, and more preferably less than about 0.5%. Below-LEL conditions may be achieved by providing adequate airflow and fluid vapor removal within the enclosure.
[0228] Next, the cast sheet can be subjected to a two-step stretching / fluid evaporation process. In the first step, the cooled shaped sheet material can be stretched in at least one direction. The first direction of stretching can be carried out in the machine direction, that is, the direction in which the initially shaped sheet material leaves the extrusion die head and the cooling roller (one or more). Stretching can be easily accomplished, for example, by passing the shaped sheet material through a nip roller (nip roller) with a set rotation rate, and then through a second group or subsequent nip roller group, followed by a take-up roller. The first machine direction stretching can be carried out in an environment lower than the LEL or higher than the UEL environment similar to the above environment. Conventional stretching techniques can be used, such as a tenter method, an expansion method, or a combination thereof. Stretching can be carried out in a uniaxial or biaxial (machine and transverse directions), but uniaxial stretching may be preferred. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential stretching, or multi-stage stretching (e.g., a combination of simultaneous biaxial stretching and sequential uniaxial stretching) can be used.
[0229] The initially formed sheet can first be stretched in a first direction (e.g., machine direction) by at least about 2 times its initial dimension, wherein stretching by about 2 to 12 times is preferred, and wherein stretching by about 3 to 8 times is more preferred. This first stretching can be performed while the sheet is maintained at an elevated temperature. The temperature can be (T m -70) to (T m -20)℃, where T m is the melt temperature of the polymers (where only one polymer is used to make the sheet material), or the higher T of two or more polymers forming a mixture of polymers used to form the sheet material. m The stretching is preferably sufficient to reestablish crystallinity in the polymer of the first stretched sheet material.
[0230] During the first step of the two-step stretching / fluid evaporation process, the residual fluid present in the sheet material can be removed by evaporation and recrystallization. The polymer of the resulting first stretched sheet material preferably has a crystallinity of at least 40% by mass, more preferably about 40 to 85% by mass, and even more preferably about 50 to 80% by mass. Further, the residual fluid in the initial stretched sheet material is preferably present at about 10 to 50% by weight of the initial formed sheet material, more preferably about 15 to 40% by weight of the initial formed sheet material. The first stretched sheet material may have a ratio of the intermediate fluid percentage to the polymer crystallinity percentage of about 0.15:1 to 1:1.
[0231] The first stretched sheet material may then be subjected to a second stretching / evaporation step. The second step may be performed by stretching the first sheet in at least one second direction, which is transverse to the direction of the first stretching. For example, when only the machine direction is used for the first stretching, the sheet material may be stretched in a direction transverse thereto for the second stretching. The stretching may be accomplished using a conventional tenter. The tenter may have a set of tracks that are capable of clamping the sheet product on both edges and pulling the sheet apart further as the sheet moves through the tenter. The second stretching may be performed in the machine and / or transverse direction, and may be performed simultaneously or sequentially with the directional stretching. The second stretching may be performed at a temperature at least about 10°C lower than the operating temperature of the first stretching step. The second stretching of the sheet material may be in one or two directions and may be about 2 to 14 times (i.e., about 200-1400%) the initial size of the first stretched sheet material.
[0232] The second step of the stretching / fluid evaporation process may also simultaneously include further evaporation and removal of the fluid remaining in the sheet material. When the stretching of the sheet material is completed, the sheet material preferably contains substantially no or only a small amount of residual fluid.
[0233] The sheet material can utilize first and second (e.g., machine and transverse) stretching to produce a sheet product. The combined stretch ratio can be at least about 4 times, preferably about 4 to 140 times, and more preferably about 8 to 80 times. Depending on the machine settings, the first stretch and the second stretch can be interchangeable when processed sequentially.
[0234] In the case where the second stretched sheet material is under tension in at least one or both stretching directions, the second stretched sheet material can be subjected to annealing or elevated temperature sheet stabilization. The annealing temperature can be about (T m -50) to (T m -5)℃, where T mThe melting temperature of the first polymer representing the sheet product. The completion of annealing may be a function of heat transfer efficiency, temperature, residence time and relaxation. The stretched sheet material can be maintained under these conditions for a period of about 1 to 300 seconds, preferably about 5 to 120 seconds. Optionally, as known in the art, the sheet product can be relaxed in one or both stretching directions (length and / or width reduced by about 5% to 20%) to further improve dimensional stability. This method anneals the sheet material to set the polymer in a fixed configuration to form a desired sheet product. The annealed sheet product can be further stored at room temperature or in a hot box environment for up to two weeks to complete dimensional stability.
[0235] After the stretching of the sheet material is completed, the residual fluid in the sheet can be removed by evaporation during annealing and / or before annealing. The residual amount of fluid can be substantially 0% by weight of the sheet product, or less than 1% by weight of the sheet product. The sheet product preferably has any second polymer uniformly distributed within the first polymer matrix network, and preferably has continuous open unit capillaries. The second polymer can be in fibril or particle form and can have a diameter of less than 1 micron, preferably less than 1 micron. More preferably less than and even more preferably less than The granularity.
[0236] Preferably, some or all of the above operations of mixing polymer(s) and fluid, cooling the sheet material, stretching the sheet material in one or two directions, and annealing can be performed in one or more enclosures to readily allow capture of any evaporated fluid. The captured vapor can then be subjected to condensation, collection or recycling for use as the first fluid or can be used as fuel for heating stretching rollers, tenter frames or annealing furnaces.
[0237] Finally, by using a low molecular weight organic fluid with a high vapor pressure and low boiling point as described herein, and removing the fluid by evaporating the fluid from the sheet material to ultimately form a resulting sheet product, the desired sheet product can be obtained while reusing the fluid. As a result, waste streams - common in other known methods of removing an initial fluid by extraction with a secondary fluid - can be reduced or eliminated by the present process, thereby providing environmental and economic benefits.
[0238] Reference now Figure 2 , shows a simplified schematic side view of one embodiment of a system for making a microporous sheet product according to the present invention, which is generally indicated by reference numeral 111. For clarity, simplicity and / or ease of description, certain details of system 111 discussed elsewhere in this application or not important to understanding the present invention may be omitted from this description and / or may be included. Figure 2 may be omitted or may be shown therein in a simplified manner.
[0239] The system 111 can include an extruder 113, which can be conventional and / or of the type described above. A die head 115, which can be conventional and / or of the type described above, can be coupled to the outlet end of the extruder 113. An extrudate or cast sheet 116 can be discharged from the die head 115.
[0240] The system 111 may further include a housing 117. The housing 117, which may be made of a substantially gas-impermeable material, may be formed to include a first inlet 119, a second inlet 121, a first outlet 123, and a second outlet 125. The first inlet 119 may be appropriately positioned and sized to receive the outlet end of the die head 115 so that the cast sheet 116 can be introduced into the housing 117. The second inlet 121 may be fluidly coupled to an outlet end of an inert gas source or purge device 129, which may be used at process startup or as needed to reduce the oxygen concentration within the housing 117. Examples of inert gases that may be present in the purge 129 may include nitrogen or carbon dioxide gas. The first outlet 123 may be appropriately positioned and sized to allow overflow gas to escape from the housing 117.
[0241] The interior of the enclosure 117 may contain a first gas zone, and vapors of an organic fluid (such as, but not limited to, vapors of the first fluid from the cast sheet 116) may be allowed to accumulate in the first gas zone to a concentration above the upper explosion limit. Depending on the size of the enclosure 117 and / or its design, the vapor concentration of the organic fluid may be very high at the first inlet 119 and / or the sheet 116 location, but may exhibit much lower vapor concentrations (one or more) at certain static locations such as within the first outlet 123 and the second outlet 125 due to vapor outflow and / or air inflow. As described above, in some cases, this lower vapor concentration may be lower than above the UEL condition.
[0242] The housing 117 may be appropriately sized to receive a plurality of rollers. Such a plurality of rollers may include, for example, a first roller 131, a second roller 133, and a third roller 135. The first roller 131, which may be a chilled roll, and the second roller 133, which may be a chilled roll, may be co-arranged within the housing 117 in an S-shaped roll-wrapped configuration, with the winding side of the first roller 131 aligned with the first inlet 119. The third roller 135 may have an outlet side aligned with the second outlet 125.
[0243] The system 111 further may include one or more jacks 141 that may be used to raise or otherwise adjust the level of the housing 117 .
[0244] The system 111 can further include a guide roller 145, a pair of pulling rollers 147-1 and 147-2, and a wind-up roller 149. The guide roller 145 can have a wind-up side aligned with the second outlet 125 so that it can receive the cooled cast sheet 116. The pulling rollers 147-1 and 147-2 can be used to stretch the cooled cast sheet 116 in a two-step stretching process, and the wind-up roller 149 can be used to store the product in a wound state.
[0245] The space outside the housing 117, particularly the space encompassing the guide roller 145, the pulling rollers 147-1 and 147-2, and the winding roller 149, may define a second gas region. Preferably, the concentration of the organic fluid in the second gas region is at a concentration below the lower explosion limit.
[0246] It should be understood that although in the present embodiment the second gas region is not accommodated within the housing, the second gas region may be accommodated within the housing.
[0247] Reference now Figure 3 , shows a schematic side view of a first alternative casting configuration shown in system 111, which is constructed in accordance with the present invention and is indicated by reference numeral 211. For clarity, simplicity, and / or ease of description, certain details of casting configuration 211 discussed elsewhere in this application or not important to understanding the present invention may be omitted from this description and / or may be included. Figure 3 Omitted or may be shown therein in a simplified manner.
[0248] The casting configuration 211, which can be used in the system 111 in place of the rollers 131, 133, and 135 and can be considered an S-type embraced roller casting configuration, can include a chilled casting roller 213, a chilled casting roller 215, and a roller 217. It will be appreciated that since the outlet direction of the casting configuration 211 is different compared to the outlet direction of the system 111, if the casting configuration 211 is incorporated into the system 111, the second outlet 125 of the housing 117 needs to be relocated.
[0249] Reference now Figure 4 , shows a schematic side view of a second alternative casting configuration shown in system 111, which is constructed in accordance with the present invention and is indicated by reference numeral 311. For clarity, simplicity, and / or ease of description, certain details of casting configuration 311 discussed elsewhere in this application or not important to understanding the present invention may be omitted from this description and / or may be included. Figure 4 Omitted or may be shown therein in a simplified manner.
[0250] The casting configuration 311, which can be used in the system 111 in place of the rollers 131, 133, and 135 and can be considered a U-shaped embraced roller casting configuration, can include a chilled casting roller 313 and a roller 317. It will be appreciated that since the outlet direction of the casting configuration 311 is different compared to the outlet direction of the system 111, if the casting configuration 311 is incorporated into the system 111, the second outlet 125 of the housing 117 needs to be relocated.
[0251] Reference now Figure 5 , shows a schematic side view of a third alternative casting configuration shown in system 111, which is constructed in accordance with the present invention and is indicated by reference numeral 411. For clarity, simplicity, and / or ease of description, certain details of casting configuration 411 discussed elsewhere in this application or not important to understanding the present invention may be omitted from this description and / or may be included. Figure 5 Omitted or may be shown therein in a simplified manner.
[0252] Casting configuration 411, which may be used in system 111 in place of rollers 131, 133, and 135 and may be considered an S-type embraced roller casting configuration, may include chilled casting roller 413, chilled casting roller 415, and roller 417. It will be appreciated that since the outlet direction of casting configuration 411 is different compared to the outlet direction of system 111, if casting configuration 411 is incorporated into system 111, repositioning of second outlet 125 of housing 117 may be required.
[0253] The following examples are for illustrative purposes only and are not intended to limit the invention described herein or the claims appended hereto. Unless otherwise specified, all parts and percentages given in the accompanying description, examples and claims are by weight. Further, all numerical ranges provided above should be considered to specifically disclose all numerical subset ranges within each given range.
[0254] Example
[0255] Materials used:
[0256] - Polyethylene L5906 - from Lyondell-Basell, La Porta, Texas (MFI of 0.06) or Yuhwa, Seoul, Rep of Korea, grade Hiden VH035.
[0257] - Polyamide Grilamid L16, L25, CF6S - from EMS, Sumter, South Carolina or 6434B, 5034B - from Ube, Livonia, Michigan.
[0258] - Mineral spirits (MSB) - having a vapor pressure of 3 mm Hg at 20°C, available from MW Barr & Co. Inc., Memphis, Tennessee or from Citgo, Houston, Texas, having the following vapor pressure characteristics:
[0259]
[0260]
[0261] The equipment used is:
[0262] - Volumetric feeder, Model # K2MVS60, manufactured by K-Tron Corp., Sewell, New Jersey.
[0263] - Fluid pump, Neptune, Toronto, Canada, model 515AN3.
[0264] - Twin screw extruder (ZSK-30), manufactured by Coperion Corporation, Ramsey, NJ, 07466
[0265] - Cast film winder and MDO stretcher manufactured by Killion Extruders, Davis Standard Company, Pawcatuck, CT.
[0266] -Extensible TDO tensioner, manufactured by CSC Force Gauge, Agawam, MA, for transverse stretching.
[0267] - Bi-oriented tenter frame manufactured by Marshall and Williams, Woonsocket, RI.
[0268] The following procedure was used to form each of the sheet products described in the table below, as well as each of the comparative sheet products summarized in the table below.
[0269] A specified amount of polymer (one or more) is fed into a twin screw melt extruder via a volumetric feeder. The polymer (one or more) is melted in the extruder, and then a specified amount of fluid is introduced into the extruder via a metering pump. The polymer (one or more) and the fluid are mixed into a uniform fluid mixture. As specified, the total extrusion rate is set between 3 and 5 kg / hr. The cast sheet speed is 2 ft / min. The molten mixture, referred to as the extrudate, is formed into a cast sheet via a slot die. The sheet is cast to a temperature similar to Figure 4The casting roll shown in FIG. 1 is wound into a housing having a die head enclosed therein and having a 10 mm slot opening into which the die or molten extrudate can enter. A first fluid vapor is trapped therein, creating above UEL conditions. The vapor is then supersaturated and condensed onto a set of cooled S-shaped wrap casting rolls. The extrudate cast sheet first contacts this above UEL vapor region prior to the casting rolls. One surface of the cast sheet contacts the first roll, and a second and opposite surface of the cast sheet contacts the second roll, wherein both surfaces are cooled.
[0270] The rollers are maintained at 50°C, and the condensate is formed from the same fluid used to form the polymer / fluid mixture. The molten sheet material transitions from a liquid phase to a solid phase sheet material. After this liquid-to-solid transition, the sheet leaves the closed injection molding tank via the second slot opening, and the vapor conditions change from the above UEL region inside the tank to the below LEL region outside the tank.
[0271] The sheet is sequentially stretched in the machine direction using a series of nip rolls, wherein each stretch is performed at a controlled temperature. Each stretching operation is performed in a confined environment. The vapor from the first stretch is allowed to condense for collection. The first stretching / evaporation is performed at 105°C and at a ratio of 5.5:1 in the machine direction to impart crystallinity to the first polymer of the first formed sheet while allowing a predetermined degree of fluidity to remain.
[0272] The sheet was then subjected to stretching in the transverse direction using a tenter frame apparatus at controlled temperature(s).Stretching was performed at 30°C and at a 4:1 ratio in the transverse direction with a stream of air passing over the sheet material to aid in evaporation and drive off evaporated fluid.
[0273] The tenter force was adjusted to allow the sheet to be held under tension at an elevated temperature of 105°C for 2 minutes to anneal and set the sheet product. The properties of each of the formed sheet products are given in the table below.
[0274] As indicated in the table, Examples 1 and 2 show improved side-to-side oil wet-out, where surface pore size and porosity differences are minimized. In contrast, Example 3 (Comparative Example), produced in an uncontrolled conventional process, shows a significant difference in oil wet-out time, i.e., comparing the oil wet-out of the first surface to the second surface. This difference is 20 seconds, or an increase of 60%. The measure of the oil wet-out time is the time when a drop of SAE 30 motor oil changes the separator sheet product from an opaque white to a clear translucent appearance. This color change indicates the penetration rate of the oil through both surfaces of the separator. Obstruction can occur on either surface.
[0275] Example 2 was tested in a lithium battery button cell, as was the Celgard 2325 control separator. At C / 10 rate, both separators achieved a specific energy capacity of 180 mAh / g. At C / 2 rate, Example 2 achieved a specific energy capacity of 160 mAh / g, and the Celgard separator achieved a specific energy capacity of 151 mAh / g. The details of Examples 1-3 are summarized in the following table:
[0276] surface
[0277]
[0278] Some of the differences between the present invention and prior art methods are as follows: prior art methods do not address the use of the same highly volatile solvents in extrusion, resulting in above UEL compatible gas phase forming agents, to coagulate and form highly porous extruded cast sheets, further processed in a safe and efficient manner, limiting possible liquid solvent carryover in subsequent processing steps, while achieving thin, highly porous and low resistance battery separators. Further, prior art methods do not teach the use of high molecular weight polycondensates to form separators and the scavenging of water and acid molecules within the lithium cells where the polymers are cleaved, thereby reducing the molecular weight while maintaining a certain minimum molecular weight to maintain entanglement of the polymers in the polyolefin matrix. The present invention enables one to obtain a sheet product that is surprisingly easy to process and stretch, resulting in a highly uniform, uniform pore structure, producing sheets with high tensile strength and elongation, achieving the above characteristics in a cost-effective, environmentally desirable manufacturing manner, and generating little or no waste streams.
[0279] In at least some embodiments, the microporous sheet products of the present invention may include micro-surface cast sheets, and in at least some embodiments, the microporous sheet products of the present invention may be characterized by high electrolyte penetration, high wicking, and high electrolytic conductivity. In addition, in at least some embodiments, the microporous sheet products of the present invention may include polymers for scavenging water (H2O) and / or acid (often in the form of hydrofluoric acid) to inhibit gassing and corrosion of the battery.
[0280] The embodiments of the present invention described above are intended to be exemplary only, and those skilled in the art should be able to make various changes and modifications thereto without departing from the spirit of the present invention. All these changes and modifications are intended to fall within the scope of the present invention as defined by the appended claims.
Claims
1. A microporous sheet product, the microporous sheet product being prepared by a process comprising: (a) melt extruding an extrusion mixture to form a cast sheet, wherein the extrusion mixture comprises: at least one thermoplastic polymer and a compatibilizing agent, the compatibilizing agent comprising a first organic fluid; (b) cooling the cast sheet in a first gas zone, the first gas zone comprising a first organic vapor, the first organic vapor comprising the first organic fluid in vapor form, the first organic vapor being present in at least a portion of the first gas zone at a concentration above the UEL; and (c) at least some stretching of the cooled cast sheet in a second gas zone, the second gas zone comprising a second organic vapor, the second organic vapor comprising the first organic fluid in vapor form, the second organic vapor being present in the second gas zone at a concentration below the LEL.
2. The microporous sheet product of claim 1, wherein the at least one thermoplastic polymer comprises at least one polyolefin.
3. The microporous sheet product according to claim 1, wherein the compatibilizing agent is at least one selected from hydrocarbon oils, organic esters and phthalates.
4. The microporous sheet product of claim 3, wherein the compatibilizing agent has a vapor pressure of about 1 to 50 mm Hg at 70°C, a vapor pressure of about 0.1 to 5 mm Hg at 20°C, and a boiling temperature of about 170 to 250°C.
5. The microporous sheet product of claim 1, wherein the extrusion mixture consists of the at least one thermoplastic polymer and the compatibilizing agent.
6. The microporous sheet product of claim 1, wherein the first organic vapor consists of the first organic fluid in vapor form.
7. The microporous sheet product of claim 1, wherein the first organic vapor comprises the first organic fluid in vapor form and the second organic fluid in vapor form.
8. The microporous sheet product of claim 1, wherein the first gas zone is maintained at a temperature in the range of -20°C to 160°C.
9. The microporous sheet product of claim 1, wherein the first organic vapor is present in the first gas region at a concentration of at least 3% by volume.
10. The microporous sheet product of claim 1, wherein the first organic vapor is present in the first gas region at a concentration of at least 30% by volume.
11. The microporous sheet product of claim 1, wherein the first gas region is enclosed by an enclosure.
12. The microporous sheet product of claim 1, wherein a concentration ratio of the first organic vapor to oxygen in the first gas region is greater than 0.1:
1.
13. The microporous sheet product of claim 1, wherein a concentration ratio of the first organic vapor to oxygen in the first gas region is greater than 2:
1.
14. A method of manufacturing a microporous sheet product, the method comprising the steps of: (a) melt extruding an extrusion mixture to form a cast sheet, wherein the extrusion mixture comprises at least one thermoplastic polymer and a compatibilizing agent, the compatibilizing agent comprising a first organic fluid; (b) cooling the cast sheet in a first gas region, the first gas region comprising a first organic vapor, the first organic vapor comprising the first organic fluid in vapor form, the first organic vapor being present in at least a portion of the first gas region at a concentration above the UEL; and (c) subjecting the cooled cast sheet to at least some stretching in a second gas zone comprising a second organic vapor comprising the first organic fluid in vapor form, the second organic vapor being present in the second gas zone at a concentration below the LEL.
Citation Information
Patent Citations
Food casings capable of transferring a functional additive from a porous inner layer onto an encased food product
EP1911352A1
Microporous sheet product and methods for making and using the same
US10586965B2
Self-humidifying proton exchange membrane, membrane-electrode assembly, and fuel cell
US20070092777A1
Microporous film of semicrystalline polymers and method for preparing the same
US20070138682A1
Preparing Method of Microporous Polyolefin Film Through Effective Extrusion
US20100041779A1
